Resin composition
The resin composition, combining a thermoplastic resin, organized layered silicate, and hydrocarbon compound, addresses hygroscopicity and water vapor permeability issues in thermoplastic resins, ensuring low moisture absorption and mechanical stability, particularly in applications like packaging and electronics.
Patent Information
- Application Number
- JP2024097564
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-23
- Filing Date
- 2024-06-17
- Publication Date
- 2025-01-09
AI Technical Summary
Thermoplastic resins exhibit high hygroscopicity and water vapor permeability, leading to dimensional changes and mechanical property deterioration, particularly in applications where moisture absorption is a concern, such as packaging, cosmetics, and electronic equipment.
A resin composition comprising a thermoplastic resin, an organized layered silicate, and a hydrocarbon compound with 20 or more carbon atoms, where the thermoplastic resin has a solubility parameter of 9.0 to 12.5 (cal/cm³)¹⁄₂, the hydrocarbon compound has a melting point of 35°C to 180°C, and the content of the thermoplastic resin is between 15% to 90% by weight, with specific ratios of layered silicate and hydrocarbon compound to achieve low water vapor permeability and moisture absorption.
The resin composition demonstrates low water vapor permeability, low moisture absorption, and improved mechanical properties, preventing component bleed-out and appearance defects, suitable for applications requiring biodegradability and stability in varying humidity conditions.
Smart Images

Figure 2025003372000001 
Figure 2025003372000002 
Figure 2025003372000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition. [Background technology]
[0002] Thermoplastic resins, including polyethylene resin, polypropylene resin, polyester resin, polyamide resin, thermoplastic polyimide resin, and thermoplastic polyurethane resin, are molded by various molding methods, and the molded products obtained are used in a wide range of applications, such as packaging, cosmetics, sanitary products, agriculture, electronic devices, etc. Among thermoplastic resins, thermoplastic resins (polyester resin, polyamide resin, thermoplastic polyimide resin, thermoplastic polyurethane resin, polycarbonate resin, polyacetal resin, etc.) having polar groups {(carbonic acid) ester bond, amide bond, imide bond, urethane bond, ether bond, etc.} have various functions according to the functional group, but since the polar groups have high affinity for water and are hygroscopic, they are unsuitable as materials for applications in which dimensional changes and deterioration of electrical properties due to moisture absorption are problems, such as electronic device applications. For example, Patent Document 1 proposes a thermoplastic resin composition containing 0.5 to 45 parts by weight of a layered silicate that has been made organic by an organic onium ion having a specific structure, relative to 100 parts by weight of a thermoplastic resin such as a polyimide resin. The resin composition described in Patent Document 1 has a reduced water absorption rate and a reduced dimensional change under high humidity conditions compared to the thermoplastic resin alone, but the mechanical properties (such as abrasion resistance) are reduced and the practical usability is insufficient. In addition, the dimensional change is evaluated by measuring the dimensions after leaving it for 24 hours under conditions of 50°C-80% RH, but it is not evaluated for a longer period or under higher humidity conditions, and there is room for improvement in the dimensional stability upon moisture absorption.
[0003] Thermoplastic resins are also widely used as various coating agents and sealants in addition to molded products. In coating agents and sealants, the high hygroscopicity and water vapor permeability of the thermoplastic resins may be problematic depending on the application, and methods for appropriately reducing the hygroscopicity and water vapor permeability have been studied. For example, reduction of hygroscopicity has been studied in the application of coating agents (coating layers) for slowly soluble drugs (drugs that slowly release active ingredients), which are very useful in the fields of medicines, agriculture, food additives, cosmetics, sanitary products, etc. Patent Document 2 proposes a coating layer for a coated granular fertilizer containing 5% by weight to 80% by weight of aliphatic polyester and 20% by weight to 95% by weight of polyolefin wax. It is disclosed that the coated fertilizer having the coating layer described in Patent Document 2 has a wide range of control over the release of fertilizer components by controlling the hygroscopicity and moisture permeability of the coating layer to be appropriately low. However, depending on the storage and use conditions, the polyolefin wax may bleed out, causing deterioration in handleability and reducing the controllability of the release of fertilizer components. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2004-323797 A [Patent Document 2] Japanese Patent Application Publication No. 9-263476 Summary of the Invention [Problem to be solved by the invention]
[0005] The object of the present invention is to provide a resin composition containing a thermoplastic resin that combines low water vapor permeability and low moisture absorption with mechanical properties (particularly abrasion resistance), and that does not suffer from performance degradation or poor appearance due to bleed-out of the components. [Means for solving the problem]
[0006] The present inventors have conducted extensive research to solve the above problems and have arrived at the present invention. That is, the present invention is a resin composition containing a thermoplastic resin (A), an organically modified layered silicate (B), and a hydrocarbon compound (C) having 20 or more carbon atoms, and the resin composition satisfies all of the following (1) to (3): (1) The content of (A) in the resin composition is 15% by weight or more and 90% by weight or less based on the total weight of (A), (B) and (C). (2) The solubility parameter of (A) is 9.0 to 12.5 (cal / cm 3 ) 1 / 2 It is. (3) The melting point of (C) is 35°C or higher and 180°C or lower. Effect of the Invention
[0007] The resin composition of the present invention has low water vapor permeability and low moisture absorption, as well as mechanical properties (particularly abrasion resistance), and does not cause bleeding out of the components, thereby preventing performance degradation and poor appearance due to bleeding out of the components. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The resin composition of the present invention contains a thermoplastic resin (A), an organically modified layered silicate (B), and a hydrocarbon compound (C) having 20 or more carbon atoms, and satisfies all of the above (1) to (3). The thermoplastic resin (A), the organically modified layered silicate (B), the hydrocarbon compound having 20 or more carbon atoms (C), and the resin composition of the present invention will be described in this order below.
[0009] <Thermoplastic resin (A)> The thermoplastic resin (A) in the present invention has a solubility parameter (hereinafter sometimes referred to as SP value) of 9.0 to 12.5 (cal / cm 3 ) 1 / 2 It is a thermoplastic resin. In this specification, the solubility parameter means a value calculated by the formula (28) on page 153 of the method by Fedors [Polymer Engineering and Science, February, 1974, Vol. 14, No. 2, pp. 147-154] using the values (heat of vaporization and molar volume at 25°C of atoms or functional groups) listed on page 152 (Table. 5) of the same. The solubility parameter of the thermoplastic resin (A) is preferably 9.1 to 11.5 (cal / cm) from the viewpoints of dispersibility of the organically modified layered silicate (B) and affinity with the hydrocarbon compound (C). 3 ) 1 / 2 and more preferably 10.0 to 11.5 (cal / cm 3 ) 1 / 2 The solubility parameter is 9.0 (cal / cm 3 ) 1 / 2 Thermoplastic resins with a viscosity of less than 12.5 (cal / cm 3 ) 1 / 2 If it exceeds this amount, the affinity between (A) and the hydrocarbon compound (C) deteriorates, and various physical properties of the resin composition of the present invention deteriorate.
[0010] Preferred examples of the thermoplastic resin (A) include thermoplastic resins having polar functional groups, such as ester group-containing thermoplastic resin (A1), urethane group-containing thermoplastic resin (A2), amide group-containing thermoplastic resin (A3) and imide group-containing thermoplastic resin (A4). (A) may be one type of thermoplastic resin used alone or two or more types of thermoplastic resins used in combination. When two or more types of thermoplastic resins are mixed, the mixture may satisfy the above solubility parameter requirements.
[0011] The ester group-containing thermoplastic resin (A1) is a thermoplastic resin having one or more ester groups in the molecule, and examples thereof include an aliphatic polyester resin (A11), an aliphatic-aromatic polyester resin (A12), and an aromatic polyester resin (A13). Among (A1), (A11) and (A12) are preferred from the viewpoint of biodegradability.
[0012] Examples of the aliphatic polyester resin (A11) include poly(hydroxyalkanoic acid) (A111), natural product ester resin (A112), and polycondensates of aliphatic diols and aliphatic dicarboxylic acids (A113).
[0013] Poly(hydroxyalkanoic acids) (A111) include polylactic acid (PLA), polyglycolic acid (PGA), polyhydroxybutyric acid (PHB), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH), and polycaprolactone (PCL). Examples of the natural product ester resin (A112) include rosin ester resins {rosin esters obtained by esterifying rosins and hydrogenated rosin esters obtained by hydrogenating and esterifying rosins} and cellulose ester resins {cellulose acetate and cellulose esters obtained by esterifying (acetylating) celluloses}.
[0014] Examples of the polycondensates (A113) of aliphatic diols and aliphatic dicarboxylic acids include polyethylene succinate (PES), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), and polycondensates of aliphatic diols having 2 to 6 carbon atoms and aliphatic dicarboxylic acids having 3 to 8 carbon atoms (including the carbon of the carboxyl group) and their ester-forming derivatives (acid anhydrides, lower alkyl esters, acid halides, etc.). Examples of the aliphatic diol having 2 to 6 carbon atoms include ethanediol, propanediol, butanediol, dimethylpropanediol, pentanediol, and hexanediol. Examples of the aliphatic dicarboxylic acid having 3 to 8 carbon atoms (including the carbon atom of the carboxyl group) include succinic acid, malonic acid, glutaric acid, adipic acid, suberic acid, maleic acid, and fumaric acid.
[0015] The aliphatic-aromatic polyester resin (A12) is a polyester resin in which a part of the diol and / or dicarboxylic acid constituting the above-mentioned aliphatic polyester resin (A1) is replaced with an aromatic compound, and is preferably a polyester resin having aliphatic diol, aromatic dicarboxylic acids and aliphatic dicarboxylic acids as constituent units, in which a part of the aliphatic dicarboxylic acids in the above-mentioned polycondensate (A113) of aliphatic diol and aliphatic dicarboxylic acids is replaced with aromatic dicarboxylic acids. Examples of aromatic dicarboxylic acids include aromatic dicarboxylic acids having 8 to 10 carbon atoms (including the carbon of the carboxyl group) (for example, phthalic acid, phthalic anhydride, isophthalic acid, dimethylisophthalic acid, terephthalic acid, and dimethylterephthalic acid). Specific examples of (A2) include polybutylene adipate / terephthalate (PBAT), polybutylene succinate / terephthalate (PBST), and polyethylene terephthalate succinate (PETS).
[0016] Examples of the aromatic polyester resin (A13) include polycondensates of aromatic diols and the above-mentioned aromatic dicarboxylic acids. The aromatic diol is preferably an aromatic diol having 6 to 20 carbon atoms, and examples thereof include xylylene glycol, 4,4'-dihydroxybiphenyl, 2,2-bis(4'-hydroxyphenyl)propane, 2,2-bis(4'-β-hydroxyethoxyphenyl)propane, bis(4-hydroxyphenyl)sulfone, and bis(4-β-hydroxyethoxyphenyl)sulfonic acid.
[0017] The urethane group-containing thermoplastic resin (A2) is a thermoplastic resin having one or more urethane groups in the molecule, and is preferably a thermoplastic resin obtained by the reaction of a diol compound with a diisocyanate compound. Specific examples of (A2) include polyester-based thermoplastic urethane resins (A21), polyether-based thermoplastic urethane resins (A22), and polyether polyester-based thermoplastic urethane resins (A23). Among (A2), polyester-based thermoplastic urethane resin (A21) is preferred from the viewpoint of biodegradability.
[0018] The polyester-based thermoplastic urethane resin (A21) is a urethane group-containing thermoplastic resin obtained by using a reaction product of a polyester diol and a diisocyanate compound as the diol compound. Examples of the polyester diol include polycaprolactone diol and condensation type polyester diol (obtained by polycondensation of the short chain diol compound described below with a dicarboxylic acid having 2 to 20 carbon atoms or an ester-forming derivative thereof). Examples of the dicarboxylic acid having 2 to 20 carbon atoms or its ester-forming derivative, which is a raw material for the condensed polyester diol, include aliphatic dicarboxylic acids (succinic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, octadecanedicarboxylic acid, decylsuccinic acid, fumaric acid, maleic acid, etc.), alicyclic dicarboxylic acids (dimer acid, etc.), aromatic dicarboxylic acids (terephthalic acid, isophthalic acid, phthalic acid, t-butylisophthalic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-biphenyldicarboxylic acid, etc.), and acid anhydrides and acid halides thereof.
[0019] The polyether-based thermoplastic urethane resin (A22) is a urethane group-containing thermoplastic resin obtained by using a reaction product of a polyether diol and a diisocyanate compound as the diol compound. Examples of the polyether diol include compounds in which an alkylene oxide having 2 to 30 carbon atoms is added to a compound containing two active hydrogens (such as the short-chain diol compounds described below, diamines, dicarboxylic acids, and phosphoric acids), and specific examples thereof include polytetramethylene glycol, polypropylene glycol, and polyethylene glycol.
[0020] The polyether polyester thermoplastic urethane resin (A23) is a urethane group-containing thermoplastic resin obtained by using a reaction product of a polyether polyester diol as a diol compound and a diisocyanate compound. Examples of the polyether polyester diol include condensation polymers of the polyether diol and the dicarboxylic acid having 2 to 20 carbon atoms or an ester-forming derivative thereof, which are given as examples of the raw material for the condensation type polyester diol.
[0021] The urethane group-containing thermoplastic resin (A2) is preferably a reaction product of a long-chain diol compound, a diisocyanate compound and a short-chain diol compound. The long-chain diol compound is a diol compound having a number average molecular weight (hereinafter sometimes referred to as Mn) of 500 or more, and preferably a diol compound having a number average molecular weight of 500 to 3,000. The short-chain diol compound is a diol compound having an Mn or a chemical formula weight of less than 500. Specific examples include ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, bisphenol A, and an ethylene glycol adduct of bisphenol A. Examples of the diisocyanate compound include toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), hydrogenated diphenylmethane diisocyanate (HMDI), isophorone diisocyanate (IPDI), and hexamethylene diisocyanate (HDI).
[0022] The number average molecular weight (Mn) of the long-chain diol compound and the short-chain diol compound can be measured by gel permeation chromatography under the following conditions, for example. Apparatus: "Waters Alliance 2695" [Waters] Column: "Guardcolumn Super HL" (1 column), "TSKgel SuperH2000, TSKgel SuperH3000, TSKgel SuperH4000 (all manufactured by Tosoh Corporation) connected together" Sample solution: 0.25% by weight dimethylformamide solution Solution injection volume: 10μl Flow rate: 0.6ml / min Measurement temperature: 40℃ Detector: Refractive index detector Reference material: Standard polyethylene glycol
[0023] The reaction product of the long-chain diol compound, the diisocyanate compound, and the short-chain diol compound can be synthesized by a known method. For example, it can be synthesized by a method of synthesizing a prepolymer having an isocyanate group at the end by reacting the long-chain diol compound with the diisocyanate, and then adding the short-chain diol compound (chain-extended prepolymer method), or by a method of simultaneously mixing and polymerizing the long-chain diol compound, the short-chain diol compound, and the diisocyanate compound (one-shot method).
[0024] The amide group-containing thermoplastic resin (A3) is a thermoplastic resin having one or more amide groups in the molecule, and examples thereof include aliphatic polyamide resins (A31), semi-aromatic polyamide resins (A32) and wholly aromatic polyamide resins (A33). Among the amide group-containing thermoplastic resins (A3), aliphatic polyamide resins (A31) are preferred from the viewpoint of biodegradability.
[0025] The aliphatic polyamide resin (A31) means a polyamide resin whose constituent raw materials are all aliphatic compounds, and includes polyamide resins whose structural units are lactam and / or aminocarboxylic acid, polyamide resins obtained by reacting aliphatic dicarboxylic acids with aliphatic diamines, and aliphatic polyester polyamide resins whose constituent raw materials are lactam and / or aminocarboxylic acid, aliphatic dicarboxylic acid, and polyether diol. Specific examples of commercially available (A31) include nylon 6 (PA6), nylon 66 (PA66), nylon 11 (PA11), and nylon 12 (PA12). The aliphatic polyester polyamide resin can also be obtained by known methods such as the reaction of the aliphatic polyester resin (A11) with a lactam and / or an aminocarboxylic acid, the reaction of the aliphatic diol, an aliphatic dicarboxylic acid, and a lactam and / or an aminocarboxylic acid, the reaction using the ester-amide exchange reaction described in JP-A-07-157557, and the method described in JP-A-2007-060234.
[0026] Examples of aminocarboxylic acids constituting the aliphatic polyester polyamide resin include amino acids [glycine, 2-aminopropanoic acid (alanine), methionine, valine, leucine, 2-amino-3-methylpentanoic acid (isoleucine), etc.], 11-aminoundecanoic acid, and 12-aminododecanoic acid, while examples of lactams include cyclic compounds formed by intramolecular dehydration and condensation of aminocarboxylic acids, such as ε-caprolactam, 11-undecanelactam, and 12-laurolactam. Examples of the aliphatic dicarboxylic acid include aliphatic dicarboxylic acids having 2 to 20 carbon atoms (succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, maleic acid, fumaric acid, itaconic acid, etc.), and alicyclic dicarboxylic acids having 5 to 20 carbon atoms (cyclopropanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, cyclohexenedicarboxylic acid, bicyclohexyl-4,4'-dicarboxylic acid, camphoric acid, etc.). As the above aliphatic diamine, those having 2 to 12 carbon atoms can be preferably used, and specific examples thereof include ethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, and decamethylenediamine. Examples of polyether diols used as a raw material for the aliphatic polyester polyamide resin include those exemplified as the raw material for (A2) above.
[0027] Semi-aromatic polyamide resin (A32) means a polyamide resin in which a part of the constituent raw materials is an aromatic compound, and includes a polyamide resin obtained by reacting a dicarboxylic acid with a diamine, in which either the dicarboxylic acid or the diamine is an aromatic compound (a polyamide resin obtained by reacting an aromatic dicarboxylic acid with an aliphatic diamine, or a polyamide resin obtained by reacting an aliphatic dicarboxylic acid with an aromatic diamine), and a polyester polyamide resin whose constituent raw materials are lactam and / or aminocarboxylic acid and aromatic dicarboxylic acid and / or aromatic diol. A specific example of commercially available (A32) is polymetaxylylene adipamide (PARA), etc. Examples of the aromatic dicarboxylic acid include aromatic dicarboxylic acids having 8 to 20 carbon atoms (such as terephthalic acid, phthalic acid, 2,6- or 2,7-naphthalenedicarboxylic acid, diphenyl-4,4'-dicarboxylic acid, diphenoxyethanedicarboxylic acid, tolylenedicarboxylic acid, xylylenedicarboxylic acid, and 5-sulfoisophthalic acid). Examples of the aromatic diamine include phenylenediamine compounds (1,4-phenylenediamine, 1,2-phenylenediamine, 1,3-phenylenediamine, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,5-diaminobiphenyl, and 2,4,5,6-tetrafluoro-1,3-phenylenediamine, etc.), naphthalenediamine compounds (1,5-diaminonaphthalene, 1,8-diaminonaphthalene, 2,6-diaminonaphthalene, and 2,3-diaminonaphthalene, etc.), dianiline compounds, Substances {4,4'-diamino-2,2'-ditrifluoromethyl-1,1'-biphenyl, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfide, 4-aminophenyl 4-aminobenzoate, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene benzene, 2,2-bis(4-aminophenyl)propane, 4,4'-(hexafluoroisopropylidene)dianiline, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, α,α-bis[4-(4-aminophenoxy)phenyl]-1,3-diisopropylbenzene, α,α-bis[4-(4-aminophenoxy)phenyl]-1,4-diisopropylbenzene, 4,4'-(9-fluoroisopropylidene)dianiline, 2,2-bis(3-methyl-4-aminophenyl)benzene, 4,4'-diamino-3,3'-dimethyl-1,1'-biphenyl, 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl, 9,9'-bis(3-methyl-4-aminophenyl)fluorene, 5-(4-aminophenoxy)-3-[4-(4-aminophenoxy)phenyl]-1,1,3-trimethylindane, and the like. The aliphatic diamine, aliphatic carboxylic acid, lactam, aminocarboxylic acid and aromatic diol may be the same as those exemplified above. When an aminocarboxylic acid is used as a constituent raw material of the semi-aromatic polyamide resin, an amino acid having an aromatic ring, such as phenylalanine, can also be preferably used.
[0028] The wholly aromatic polyamide resin (A33) is a polyamide resin obtained by reacting an aromatic dicarboxylic acid with an aromatic diamine.
[0029] The imide group-containing thermoplastic resin (A4) is a thermoplastic resin having one or more imide groups in the molecule, and examples thereof include an aliphatic-aromatic polyimide resin (A41). Among (A4), from the viewpoint of biodegradability, aliphatic-aromatic polyimide resin (A41) is preferable.
[0030] The aliphatic-aromatic polyimide resin (A41) is a polyimide resin obtained by an imidization reaction between an aliphatic diamine and an acid anhydride. Examples of the aliphatic diamine include linear aliphatic diamine compounds such as 1,2-ethylenediamine, 1,2-diaminopropane, 1,3-diaminopropane, 1,4-diaminobutane, 1,6-hexamethylenediamine, 1,5-diaminopentane, and 1,10-diaminodecane; branched aliphatic diamine compounds such as 1,2-diamino-2-methylpropane, 2,3-diamino-2,3-butane, and 2-methyl-1,5-diaminopentane; alicyclic diamine compounds such as 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,4-diaminocyclohexane, and 4,4'-methylenebis(cyclohexylamine); and dimer acid type diamines. Examples of the acid anhydride include benzenetetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, anthracenetetracarboxylic dianhydride, and diphthalic dianhydride.
[0031] As the thermoplastic resin (A) in the present invention, from the viewpoint of biodegradability of the resin composition, a thermoplastic resin having an ester group {ester group-containing thermoplastic resin (A1), polyester-based thermoplastic urethane resin (A21), aliphatic polyester polyamide resin, etc.} can be preferably used, and the weight proportion of the ester group (ester group concentration) of the thermoplastic resin (A) is preferably 0.1 g / g or more and 1 g / g or less based on the weight of the (A), from the viewpoints of biodegradability, low moisture absorption, low water vapor permeability, etc. of the resin composition. The ester group concentration (g / g) of (A) can be calculated from the number of ester groups [-C(=O)O-] contained in (A) and is defined as the weight (g) of the ester groups present in 1 g of (A). The ester group concentration (g / g) of (A) can be calculated by measuring infrared spectroscopy (IR) of (A) and using the intensity of the peak derived from the ester group and a calibration curve (plotting the relationship between the peak intensity and the ester group concentration) prepared using samples with known ester group concentrations, or by placing (A) and ion-exchanged water of the same weight as (A) in an autoclave and reacting at 180°C for 6 hours to hydrolyze the ester group in (A), measuring the acid value and hydroxyl value of (A) after the reaction, and calculating the ester group concentration in (A) based on the acid value and hydroxyl value. The ester group concentration (g / g) of (A) may also be calculated by determining the number of ester groups [-C(=O)O-] present in (A) from the ratio of the amounts of raw materials used in the production of (A).
[0032] The thermoplastic resin (A) in the present invention may have an amide group and / or an imide group. When the thermoplastic resin (A) has an amide group and / or an imide group, the total weight ratio (total concentration) of the amide group and the imide group is preferably 1 g / g or less based on the weight of the (A), from the viewpoints of biodegradability, low moisture absorption, low water vapor permeability, etc. of the resin composition. The total concentration (g / g) of amide groups and imide groups in (A) can be calculated from the number of structures [-C(=O)N-] (formula weight 42) in the amide groups and imide groups in (A), and is defined as the total weight (g) of the amide groups and structures [-C(=O)N-] in the imide groups present in 1 g of (A). The total concentration (g / g) of amide groups and imide groups in (A) can be calculated using the intensities of peaks derived from acyl groups in the amide groups and imide groups and a calibration curve (plot of the relationship between peak intensity and acyl group concentration) prepared using samples with known acyl group concentrations by infrared spectroscopy (IR) of (A); alternatively, (A) and the same weight of ion-exchanged water as (A) are placed in an autoclave and reacted at 180°C for 6 hours to hydrolyze the amide groups and imide groups in (A), and the amino group content and carboxyl group content of (A) after the reaction are measured by NMR, IR, etc., and calculation is performed based on these values. Alternatively, the total concentration (g / g) of amide groups and imide groups in (A) may be calculated by determining the number of structures [-C(=O)N-] in the amide groups and imide groups present in (A) from the quantitative ratio of the raw materials used in the production of (A).
[0033] The total concentration of ester groups, amide groups and imide groups in the thermoplastic resin (A) in the present invention is preferably 0.1 g / g or more, more preferably 0.1 to 1 g / g, and particularly preferably 0.2 to 0.8 g / g, based on the weight of the (A), from the viewpoints of biodegradability, low moisture absorption and low water vapor permeability of the resin composition.
[0034] From the viewpoints of biodegradability and abrasion resistance, the glass transition temperature (hereinafter sometimes referred to as Tg) of the thermoplastic resin (A) is preferably -70°C or higher and 150°C or lower, and more preferably -70°C or higher and 70°C or lower. The glass transition temperature (° C.) of the thermoplastic resin (A) is a value measured and calculated by the following method.
[0035] <Method of measuring and calculating glass transition temperature> Using a DSC measuring device according to JIS K7121, about 10 mg of sample (A) is heated from 20°C to 200°C at a rate of 20°C / min under conditions of a nitrogen gas flow rate of 50 mL / min [first heating], and after reaching 200°C, it is held for 3 minutes and then cooled to -100°C at a rate of 20°C / min [second heating]. Next, the temperature is raised from -100°C to 200°C at a rate of 20°C / min [second heating]. The extrapolated glass transition onset temperature (Tig) (°C), which is the temperature of the intersection between the straight line extending the low-temperature side baseline of the DSC curve drawn during the second heating to the high-temperature side and the tangent drawn at the point where the gradient of the curve of the stepwise change part of the glass transition is maximum, is defined as the glass transition temperature (°C) in the present invention.
[0036] Among the thermoplastic resins (A), from the viewpoint of biodegradability, the ester group-containing thermoplastic resin (A1) is particularly preferred, and it is more preferred that the resin is biodegradable, that is, that the ester bonds in the molecule are hydrolyzed by moisture in the environment to lower the molecular weight, and then the resin can be further decomposed by microorganisms, enzymatic decomposition, or ingested by living organisms, and it is most preferred that the resin can be ultimately decomposed into water and carbon dioxide. When (A) is a biodegradable resin, the resin composition of the present invention can be suitably used for applications requiring biodegradability, which will be described later.
[0037] <Organic Layered Silicate (B)> The organically modified layered silicate (B) in the present invention includes layered silicates having an organic compound between layers of the layered silicate, layered silicates having organic groups on the surface of the layered silicate, and layered silicates having an organic compound between layers and having organic groups on the surface.
[0038] Examples of the layered silicate constituting the organic layered silicate (B) include talc, smectite minerals {bentonite (including those purified to only the main component montmorillonite), hectorite, fluorine hectorite, saponite, etc.}, mica, vermiculite, brittle mica, etc. In particular, smectite minerals having an electric charge between layers (montmorillonite, hectorite, fluorine hectorite, saponite, etc.), mica, vermiculite, and brittle mica are preferred.
[0039] Examples of layered silicates having an organic compound between layers of the layered silicate include organically modified layered silicate (B1) in which interlayer metal ions of the layered silicate are ion-exchanged with organic cations, and organically modified layered silicate (B2) having a polyether compound between layers of the layered silicate.
[0040] Examples of the organic cation constituting the organically modified layered silicate (B1) include a primary ammonium ion, a secondary ammonium ion, a tertiary ammonium ion, an amino acid derivative, a quaternary ammonium ion, an organic phosphonium ion, an organic pyridinium ion, and an organic sulfonium ion.
[0041] Examples of the primary ammonium ion include an octyl ammonium ion, a lauryl ammonium ion, a tetradecyl ammonium ion, a hexadecyl ammonium ion, a stearyl ammonium ion, an oleyl ammonium ion, a benzyl ammonium ion, and an anilinium ion. Examples of the secondary ammonium ion include a dilauryl ammonium ion, a ditetradecyl ammonium ion, a dihexadecyl ammonium ion, a distearyl ammonium ion, and an N-methylanilinium ion. Examples of tertiary ammonium ions include dimethyloctyl ammonium ion, dimethyldecyl ammonium ion, dimethyllauryl ammonium ion, dimethylmyristyl ammonium ion, dimethylpalmityl ammonium ion, dimethylstearyl ammonium ion, dilauryl monomethyl ammonium ion, tributyl ammonium ion, trioctyl ammonium ion, and N,N-dimethylanilinium ion. Examples of amino acid derivatives include ammonium ion of 12-aminolauryl carboxylate, ammonium ion of N,N-dimethyl-6-aminohexyl carboxylate, ammonium ion of Nn-dodecyl-N,N-dimethyl 10-aminodecyl carboxylate, and ammonium ion of dimethyl-N-12 aminolauryl carboxylate.
[0042] Specific examples of quaternary ammonium ions include dodecyltrimethylammonium ion, lauryltrimethylammonium ion, hexadecyltrimethylammonium ion, dodecylammonium ion, dimethyldistearylammonium ion, benzyldimethylstearylammonium ion, dialkyldimethylammonium ion, tetrabutylammonium ion, tetrapentylammonium ion, tetraethylammonium ion, and triethylmethylammonium ion.
[0043] The organic phosphonium ion includes a phosphonium ion in which the nitrogen atom of the above-mentioned quaternary ammonium ion is replaced with a phosphorus atom.
[0044] The organic cation may be one type alone or a mixture of two or more types. From the viewpoints of the affinity between (A) and the hydrocarbon compound (C), the water vapor permeability of the resin composition, safety, etc., a quaternary ammonium ion is preferred.
[0045] The method for obtaining the organically modified layered silicate (B1) obtained by ion-exchanging the interlayer metal ions of the layered silicate with organic cations is not particularly limited, and can be obtained by a known method. For example, the organically modified layered silicate can be obtained by immersing the layered silicate in water, an organic solvent, or a mixed solvent of water and an organic solvent, adding a salt containing an organic cation, stirring, leaving the mixture to stand for a certain period of time, filtering, and washing and drying the obtained solid. The salt containing the organic cation may be generated in the system, and for example, a primary amine and hydrochloric acid may be added to generate a salt containing a primary ammonium ion in the system to obtain (B1). The organically modified layered silicate obtained by ion-exchanging the interlayer metal ions of the layered silicate with organic cations may be commercially available.
[0046] The salt containing an organic cation used in the method for obtaining an organically modified layered silicate (B1) by ion-exchanging interlayer metal ions of a layered silicate with an organic cation is preferably a salt of an organic cation and a counter ion (anion). From the viewpoint of reducing the impact on the environment, preferred counter ions include chloride ions, bromide ions, and acetate ions.
[0047] Examples of the polyether compound constituting the organically modified layered silicate (B2) having a polyether compound between layers of the layered silicate include polyethylene glycol and nonionic surfactants having a polyoxyethylene group. Examples of nonionic surfactants having a polyoxyethylene group include polyoxyethylene alkyl ethers, polyoxyethylene phenyl ethers, polyoxyethylene / polyoxypropylene block polymers, fatty acid polyethylene glycols, fatty acid polyoxyethylene sorbitan, and polyoxyethylene alkylamino ethers.
[0048] The method for obtaining the above-mentioned organically modified layered silicate (B2) is not particularly limited, and can be obtained by a known method. For example, the organically modified layered silicate can be obtained by immersing the layered silicate in water, an organic solvent, or a mixed solvent of water and an organic solvent (preferably a polar solvent such as alcohol, glycol, ketone, ether, amide, etc.), adding a polyether compound, stirring, leaving it for a certain period of time, and then spray drying. Furthermore, organically modified layered silicate (B2) obtained by treating a layered silicate with a polyether compound, which is commercially available, may also be used.
[0049] In (B2), the weight parts of the polyether compound relative to 100 parts by weight of the layered silicate is preferably 0.1 to 50 parts by weight, more preferably 1 to 40 parts by weight, from the viewpoints of water vapor permeability and the solubility of a slowly soluble drug when used as a coating layer for the drug.
[0050] Examples of layered silicates having an organic group on the surface of the layered silicate include organically modified layered silicates (B3) obtained by reacting a layered silicate with a coupling agent having an organic group and a reactive functional group to modify the surface of the layered silicate. The organically modified layered silicate (B3) obtained by surface-modifying a layered silicate by reacting it with a coupling agent having an organic group and a reactive functional group has an organic group derived from the coupling agent as an organic group portion on the surface of the layered silicate.
[0051] Examples of the coupling agent having an organic group and a reactive functional group include an isocyanate compound, an organosilane compound, an organotitanate compound, an organoborane compound, and an epoxy compound. Among these, from the viewpoint of reactivity with layered silicates, organic silane compounds are particularly preferred. Specific examples thereof include epoxy group-containing alkoxysilane compounds such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; mercapto group-containing alkoxysilane compounds such as γ-mercaptopropyltrimethoxysilane and γ-mercaptopropyltriethoxysilane; ureido group-containing alkoxysilane compounds such as γ-ureidopropyltriethoxysilane, γ-ureidopropyltrimethoxysilane, and γ-(2-ureidoethyl)aminopropyltrimethoxysilane; γ-isocyanatopropyltriethoxysilane, γ-isocyanatopropyltrimethoxysilane, γ-isocyanatopropylmethyldimethoxysilane, and γ-isocyanatopropylmethyldiethoxysilane. and isocyanato group-containing alkoxysilane compounds such as γ-isocyanatopropylethyldimethoxysilane, γ-isocyanatopropylethyldiethoxysilane, and γ-isocyanatopropyltrichlorosilane; amino group-containing alkoxysilane compounds such as γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, and γ-aminopropyltrimethoxysilane; hydroxyl group-containing alkoxysilane compounds such as γ-hydroxypropyltrimethoxysilane and γ-hydroxypropyltriethoxysilane; and carbon-carbon unsaturated group-containing alkoxysilane compounds such as γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, and N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane hydrochloride. Of these, carbon-carbon unsaturated group-containing alkoxysilane compounds are the most preferred.
[0052] The method for obtaining the organically modified layered silicate (B3) obtained by reacting the layered silicate with a coupling agent having an organic group and a reactive functional group to modify the surface is not particularly limited, but includes (1) a method in which the coupling agent is adsorbed on the layered silicate in a polar solvent such as water, methanol, ethanol, or a mixed solvent thereof, (2) a method in which the layered silicate is added to a high-speed stirring mixer such as a Henschel mixer, and the coupling agent or a solution of the coupling agent (a solution in which the coupling agent is diluted with water or a mixed solvent of water and an organic solvent) is dropped while stirring to allow the layered silicate to be adsorbed, and (3) a method in which the coupling agent is directly added to the layered silicate and mixed in a mortar or the like to allow the layered silicate to be adsorbed. When the layered silicate is reacted with the coupling agent, it is preferable to simultaneously mix water, acidic water, alkaline water, etc. in order to promote hydrolysis of the alkoxy group of the coupling agent. In addition, in order to increase the reaction efficiency of the coupling agent, an organic solvent that dissolves both water and the coupling agent, such as methanol or ethanol, may be mixed in addition to water. It is also possible to further promote the reaction by heat-treating the layered silicate treated with such a coupling agent. Alternatively, a method may be used in which the layered silicate is not reacted with the coupling agent in advance, but the coupling agent is added together when the layered silicate is melt-kneaded with the thermoplastic resin (A), etc., a so-called integral blend method.
[0053] In addition, by carrying out both ion exchange of interlayer metal ions of the layered silicate with organic cations and reaction with a coupling agent having an organic group and a reactive functional group, it is possible to obtain a layered silicate having an organic compound between the layers of the layered silicate and an organic group on the surface.
[0054] Among the organically modified layered silicates (B3), from the viewpoints of the water vapor permeability of the resin composition and the suppression of bleed-out of the hydrocarbon compound (C) described below, organically modified layered silicates (B3) having an organic group having 6 or more carbon atoms on their surface are preferred, and organically modified layered silicates (B3) having an organic group having 6 or more carbon atoms on their surface are more preferred. Examples of the organic group having 6 or more carbon atoms include an alkyl group having 6 or more carbon atoms, an alkylene group having 6 or more carbon atoms, an aromatic ring group (an aryl group which may have an alkyl group as a substituent), etc., and an alkyl group having 6 or more carbon atoms and an aromatic ring group are preferable. The number of carbon atoms in the above organic group part is more preferably 10 or more, and particularly preferably 20 or more. Also, from the viewpoints of water vapor permeability and hygroscopicity, a layered silicate having an organic compound between its layers is also preferable, and an organic layered silicate (B1) having a quaternary ammonium ion between its layers is more preferable. Also, a layered silicate having an organic compound between its layers and having an organic group having 6 or more carbon atoms on its surface is also preferable.
[0055] Further, from the viewpoint of the moldability of the resin composition, the swelling force in chloroform measured by changing water in the Japan Bentonite Industry Association: Standard Test Method - Swelling Test Method for Bentonite (Powder) (JBAS104:77) to chloroform is preferably 70 mL / 2 g or less, and more preferably 10 to 60 mL / 2 g for the organic layered silicate (B) in the present invention. The swelling force in chloroform measured by changing water in JBAS104:77 to chloroform can be specifically measured as follows.
[0056] <Measurement Method of Swelling Force in Chloroform Measured by Changing Water in JBAS104:77 (Swelling Test Method for Bentonite (Powder)) to Chloroform> 2.0 g of the organic layered silicate (B) is added little by little to a 100 mL stoppered graduated cylinder containing 100 mL of chloroform. At this time, the next addition is made after the added (B) has deposited on the bottom of the graduated cylinder. After the last addition, the apparent volume of the lump of the organic layered silicate (B) at the bottom of the graduated cylinder after standing at 25°C for 24 hours is read from the scale of the graduated cylinder and expressed as the swelling force (mL / 2 g) in chloroform.
[0057] The modification rate (%) of the organically modified layered silicate (B) is preferably 0.1 to 50%, more preferably 10 to 45%, from the viewpoints of water vapor permeability and the solubility of a drug when used as a coating layer for a soluble drug. The above-mentioned modification rate (%) means the ratio of the surface of the layered silicate that is organized in the organically modified layered silicate (B), i.e., the percentage of the area modified (coated) with organic groups relative to the area of the layered silicate, and is a value measured and calculated by the following method.
[0058] <Measuring and calculating the modification rate (%) of (B)> Organo-layered silicate (B) in toluene at 1.0 x 10 -3 The sample was dispersed at a concentration of 100% by mass, spin-cast onto a mica substrate, and then dried. The sample was observed in tapping mode using an atomic force microscope (SPA-300, manufactured by Seiko Instruments Inc.) The area of the layered silicate surface that was modified (covered) with organic groups was analyzed from the obtained image, and the modification rate (%) was calculated using the following formula. Modification rate (%) = area modified (covered) with organic groups / total area of layered silicate × 100
[0059] The state of modification with organic groups can be determined by determining that a site having a significant height (thickness) (1 nm or more) above the surface of the layered silicate is modified with an organic group. Specifically, the modification rate can be calculated as follows. The height and area of the layered silicate are determined using Grain Size, an analysis tool within the atomic force microscope. After calculating the area of the entire layered silicate, the part significantly higher than the surface height of the layered silicate is regarded as the part modified (coated) with organic groups, and the area modified (coated) with organic groups is calculated. The modification rate (%) is calculated by substituting these into the above formula.
[0060] The median diameter of the organically modified layered silicate (B) is preferably 0.01 to 40 μm from the viewpoints of water vapor permeability of the resin composition and ease of adjusting the solubility of a slowly soluble drug when used as a coating layer for the drug. The median diameter (μm) in the present invention is a value measured using a laser diffraction / scattering type particle size distribution measuring device (LA-300, manufactured by Horiba, Ltd.) with trichloroethylene as a dispersion medium and without ultrasonic irradiation, and the median diameter of the organically modified layered silicate (B) in the resin composition of the present invention can be measured by the following method. <Median diameter of the organically modified layered silicate (B) in the resin composition> The resin composition is dissolved in a good solvent (e.g., DMF, or a chlorine-based solvent such as trichloroethylene), and the inorganic matter is recovered by centrifugation. At this point, the solution contains the organo-modified layered silicate (B) and non-organo-modified (non-organic) layered silicate. The inorganic matter is dissolved / dispersed in a chlorine-based solvent (e.g., trichloroethylene), and the supernatant is recovered. Since non-organo-modified layered silicate does not disperse in a chlorine-based solvent (e.g., trichloroethylene), only the organo-modified layered silicate (B) is recovered. The recovered organo-modified layered silicate (B) is dispersed in trichloroethylene as a dispersion medium in the same manner as above, and measured using a laser diffraction / scattering type particle size distribution analyzer.
[0061] <Hydrocarbon compounds with 20 or more carbon atoms (C)> The hydrocarbon compound (C) having 20 or more carbon atoms in the present invention is a hydrocarbon compound having 20 or more carbon atoms and a melting point of 35° C. or more and 180° C. or less, and may be a saturated or unsaturated hydrocarbon compound. If the carbon number is less than 20, the compound tends to bleed out onto the surface of the resin composition, causing poor appearance, stickiness on the surface, and other performance degradation of the resin composition. Specific examples of the hydrocarbon compound (C) having 20 or more carbon atoms include alkanes (eicosane, henoicosane, tetracosane, triacontane, etc.), polycyclic aromatic hydrocarbons (benzopyrene, etc.), polyolefins (polyethylene, etc.), etc. In addition, petroleum waxes (paraffin wax, microcrystalline wax, petrolatum, etc.) containing hydrocarbon compounds as the main components can also be used as (C). The hydrocarbon compound (C) having 20 or more carbon atoms may be used alone or in combination of two or more.
[0062] In the resin composition of the present invention, the hydrocarbon compound (C) having 20 or more carbon atoms is contained for the purposes of reducing the moisture absorption and water vapor permeability of the resin composition, and improving the abrasion resistance. The melting point of the hydrocarbon compound (C) having 20 or more carbon atoms is 35°C or higher and 180°C or lower, as described above. If the melting point is lower than 35°C, (C) is likely to bleed out onto the surface of the resin composition. If the melting point is higher than 180°C, the compatibility or dispersibility of (C) in the thermoplastic resin (A) is likely to deteriorate. However, when two or more types of hydrocarbon compounds (C) are used in combination, the melting point of the mixture of two or more types may be within the above range. The melting point of the hydrocarbon compound (C) having 20 or more carbon atoms is preferably 35 to 100°C, more preferably 40 to 80°C, from the viewpoints of reducing water vapor permeability, improving abrasion resistance, bleed-out resistance, and compatibility or dispersibility in (A).
[0063] Moreover, the molecular weight of the hydrocarbon compound (C) having 20 or more carbon atoms is preferably 600 or less, and more preferably 500 or less, from the viewpoint of biodegradability. In the present invention, the molecular weight of the hydrocarbon compound (C) is the molecular weight calculated from the chemical formula (formula weight) when (C) is a single compound, and is the value obtained by adding up the product of the molecular weight calculated from the chemical formula of each compound and the ratio of the number of molecules of each compound (molar ratio) when (C) is a mixture of two or more compounds. In addition, when (C) is a polymer such as polyolefin, the weight average molecular weight (Mw) measured by gel permeation chromatography is used as the molecular weight.
[0064] The weight average molecular weight (Mw) of (C) in the present invention can be measured by gel permeation chromatography, for example, under the following conditions. Apparatus: "Waters Alliance 2695" [Waters] Column: Showa Denko AD806M / S (3 columns) Sample solution: 0.25% by weight solution in ortho-dichlorobenzene Solution injection volume: 10μL Flow rate: 0.6ml / min Measurement temperature: 140℃ Detector: Refractive index detector Reference material: Standard polystyrene
[0065] <Resin composition> The resin composition of the present invention is a resin composition containing the above-mentioned thermoplastic resin (A), the above-mentioned organically modified layered silicate (B), and the above-mentioned hydrocarbon compound (C) having 20 or more carbon atoms, and is a resin composition that satisfies all of the following (1) to (3): (1) The content of (A) in the resin composition is 15% by weight or more and 90% by weight or less based on the total weight of (A), (B) and (C). (2) The solubility parameter of the above (A) is 9.0 to 12.0 (cal / cm 3 ) 1 / 2 It is. (3) The melting point of the above (C) is 35°C or higher and 180°C or lower. The above (A), (B), and (C) and requirements (2) and (3) are as described above.
[0066] From the viewpoint of low water vapor permeability and low moisture absorption of the resin composition, the state of (C) in (A) in the resin composition of the present invention is preferably any one of the following states (i) to (iii). (i) (C) is dispersed in the form of particles in (A) with the maximum short side value of the minimum bounding rectangle being 40 μm or less. (ii) A state in which (C) forms a continuous layer having a width of 40 μm or less in (A). (iii) A state in which (C) is dissolved in (A) {(A) and (C) form a single phase}. Whether the state of (C) in (A) is (i), (ii), or (iii) can be confirmed by direct observation using a microscope such as a transmission electron microscope described below.
[0067] (i) The state in which (C) is dispersed in (A) in the form of particles with a maximum value of the short side of the minimum circumscribing rectangle of 40 μm or less means that (A) and (C) are not completely compatible with each other and exist in a form in which their interface is discernible (phase separation), and the discontinuous phase (C) forms a structure in which it exists like islands in the continuous phase (A), i.e., a sea-island structure, and that (C) is in the form of particles with a maximum value of the short side of the minimum circumscribing rectangle of 40 μm or less. The particulate form refers to particles of any shape or aggregates thereof, and the particle shape is not particularly limited and may be, for example, spherical, cubic, columnar, plate-like, scaly, rod-like, needle-like, fibrous, or irregular. The phase structure of the resin composition of the present invention and the maximum value of the short side of the minimum circumscribing rectangle of (C) can be confirmed by the following method using a transmission electron microscope. <Confirmation of phase structure and method for measuring the maximum value of the short side of the minimum bounding rectangle (C)> A molded product (cast film, molded film, etc.) of the resin composition was embedded in a visible light curable embedding resin (D-800, manufactured by Nissin EM Co., Ltd.), cut with an ultramicrotome (EM6, manufactured by Leica) to a thickness of 80 nm so that a cross section in the thickness direction of the molded product could be observed, and the obtained cross section was stained with ruthenium using a vacuum staining device (manufactured by Filgen Co., Ltd.).Then, the cross section was observed and photographed using a transmission electron microscope (JEM-1400Flash, manufactured by JEOL Ltd.) at an accelerating voltage of 80 kV and a magnification of 500 times (measurement field of view 100 μm × 100 μm). The captured images are imported into image analysis software (Winroof2018, Mitani Shoji Co., Ltd.), and in the case of an island-sea structure, the lengths of the short sides of all of the above (C)'s minimum circumscribing rectangles included in the measurement field of view (100 μm x 100 μm) are calculated, and the length of the longest short side is recorded. A total of five cross sections are cut out and analyzed five times in the same way, and the length of the longest short side among the five analyses is taken as the analysis value for "maximum value of the short side of the minimum circumscribing rectangle of (C)".
[0068] (ii) The state in which (C) forms a continuous layer having a width of 40 μm or less in (A) means a state in which both (A) and (C) form continuous phases, i.e., a biphasic structure is formed, and the width of the continuous layer formed by (C) is 40 μm or less. The confirmation of the phase structure and the measurement of the width of the continuous layer formed by (C) (hereinafter also referred to as the phase separation size of (C)) can be carried out by the following method using a transmission electron microscope. <Method for confirming phase structure and measuring phase separation size (C)> A molded product (cast film, molded film, etc.) of the resin composition was embedded in a visible light curable embedding resin (D-800, manufactured by Nissin EM Co., Ltd.), cut with an ultramicrotome (EM6, manufactured by Leica) to a thickness of 80 nm so that a cross section in the thickness direction of the molded product could be observed, and the obtained cross section was stained with ruthenium using a vacuum staining device (manufactured by Filgen Co., Ltd.).Then, the cross section was observed and photographed using a transmission electron microscope (JEM-1400Flash, manufactured by JEOL Ltd.) at an accelerating voltage of 80 kV and a magnification of 500 times (measurement field of view 100 μm × 100 μm). The captured image is imported into image analysis software (Winroof2018, Mitani Shoji Co., Ltd.), and in the case of a biphasic structure, five straight lines are drawn perpendicular to the cross section in the measurement field of view (100 μm × 100 μm), and the overlap length between each line and the hydrocarbon compound (C) {corresponding to the thickness of the hydrocarbon compound (C) phase} is calculated, and the longest overlap length is recorded. A total of five cross sections are cut out and analyzed five times in the same way, and the longest overlap length among the five analyses is taken as the analytical value for "phase separation size of (C)".
[0069] (iii) The state in which (C) is dissolved in (A) {that is, (A) and (C) form a single phase} means a state in which the interface between (A) and (C) cannot be recognized when observed using a transmission electron microscope (JEM-1400Flash, manufactured by JEOL Ltd.) at an accelerating voltage of 80 kV and a magnification of 500 times.
[0070] Methods for making the state of (C) in (A) any of the above-mentioned (i), (ii), and (iii) can be mentioned, for example, by selecting (C) having a relatively low melting point (e.g., 100°C or lower), by selecting an organo-modified layered silicate (B) having a quaternary ammonium ion as the organic group portion, by adjusting the weight ratio of (A) to (C) within the preferred range described below, and by coating a solution or melt-kneading (A) and (C) in the presence of (B) during the production of the resin composition.
[0071] When the cross section of the resin composition of the present invention is observed under a transmission electron microscope by the above-mentioned method, the hydrocarbon compound (C) is not stained with ruthenium and appears white, whereas the thermoplastic resin (A) is stained with ruthenium and appears pale black. In addition, organic layered silicate (B) is also dispersed in (A), but (B) is an inorganic substance that does not transmit electron beams and appears black, making it distinguishable from (C).
[0072] The content of (A) in the resin composition of the present invention is 15% by weight or more and 90% by weight or less based on the total weight of (A), (B) and (C). It is preferably 20 to 70% by weight, and more preferably 25 to 60% by weight. If the content of (A) in the resin composition is more than 90% by weight based on the total weight of (A), (B) and (C), it becomes difficult to achieve the low water vapor permeability and low moisture absorption of the resin composition, which is the object of the present invention, and if it is less than 15% by weight, it becomes difficult to reflect the properties of the thermoplastic resin (A) {functionality, biodegradability, etc. possessed by (A)} in the resin composition. The content of the above (B) in the resin composition of the present invention is preferably 3 to 70% by weight, more preferably 10 to 60% by weight, based on the total weight of the above (A), (B) and (C), from the viewpoint of achieving both low water vapor permeability and low moisture absorption and mechanical properties (particularly wear resistance). The content of the above (C) in the resin composition of the present invention is preferably 1 to 60% by weight, more preferably 3 to 50% by weight, based on the total weight of the above (A), (B) and (C), from the viewpoint of reflecting the mechanical properties (particularly the wear properties) and the properties of (A) in the resin composition.
[0073] The weight ratio of the organically modified layered silicate (B) to the hydrocarbon compound (C) in the resin composition of the present invention [(B) / (C)] is preferably 20 / 80 to 80 / 20, and more preferably 30 / 70 to 70 / 30, from the viewpoint of achieving both low water vapor permeability, low moisture absorption and abrasion resistance. The weight ratio of the thermoplastic resin (A) to the hydrocarbon compound (C) [(A) / (C)] is preferably 30 / 70 to 95 / 5, more preferably 40 / 60 to 95 / 5, and particularly preferably 40 / 60 to 90 / 10, from the viewpoints of achieving both low water vapor permeability, low moisture absorption, and mechanical properties, and further improving biodegradability. The content of (A) relative to the total weight of (A) and (B) in the resin composition of the present invention, [(A) / {(A)+(B)}], is preferably 30 to 80% by weight, and more preferably 40 to 70% by weight, from the viewpoints of moldability and moisture permeability.
[0074] The resin composition of the present invention may contain a moisture absorption regulator (D) in addition to the above (A), (B) and (C). The moisture absorption regulator (D) can be used for the purpose of further reducing the moisture absorption, as necessary, depending on the properties and intended use of the thermoplastic resin (A). The moisture absorption regulator (D) in the present invention is a crystalline ester compound having a melting point of 40°C or higher that does not fall under the above-mentioned (A). Specific examples include natural fats and oils (D1), naturally derived fatty acid ester waxes (D2), and synthetic waxes (D3).
[0075] The natural fats and oils (D1) are waxes whose main component is an ester compound of naturally occurring fatty acid and glycerin. Specific examples include candelilla wax, carnauba wax, rice wax, beeswax, and sunflower wax. The naturally occurring fatty acid ester wax (D2) is a wax that does not fall under the category of the aliphatic polyester resin (A11) and that contains as its main component an ester compound of a naturally occurring fatty acid and an alcohol other than glycerin. Specific examples include natural plant waxes {candelilla wax, carnauba wax, rice bran wax, Japan wax, etc.}, natural animal waxes {beeswax, shellac wax, lanolin wax, whale wax, etc.}, and natural mineral waxes {montan wax, ozokerite, ceresin, etc.}. The synthetic wax (D3) is a monohydric or polyhydric (dihydric to tetrahydric) ester compound of a carboxylic acid having 2 to 34 carbon atoms (including the carbon of the carboxyl group) and an alcohol having 1 to 36 carbon atoms, and includes those synthesized from a carboxylic acid and an alcohol, as well as those obtained by refining the above (D1) or (D2), etc. As the carboxylic acid having 2 to 34 carbon atoms (including the carbon atom of the carboxyl group), a fatty acid having 10 to 24 carbon atoms is particularly preferred, and specific examples include caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, oleic acid, sebacic acid, and montanic acid. Specific examples of alcohols having 1 to 36 carbon atoms include monohydric aliphatic alcohols such as methanol, ethanol, propanol, isopropanol, butanol, capryl alcohol, lauryl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, behenyl alcohol, gedelyl alcohol, and oleyl alcohol; and polyhydric aliphatic alcohols such as glycerin, ethylene glycol, propylene glycol, dodecanediol, sorbitol, and pentaerythritol. Specific examples of the synthetic wax (D3) include cetyl myristate, stearyl stearate, and behenyl behenate. The moisture absorption regulator (D) may be used alone or in combination of two or more kinds.
[0076] The content of the above (D) in the resin composition of the present invention is preferably 45% by weight or less based on the total weight of the above (A), (B) and (C) from the viewpoints of bleed-out resistance, mechanical strength, etc. The weight ratio of the moisture absorption regulator (D) to the thermoplastic resin (A) in the resin composition of the present invention [(D) / (A)] is preferably 0 / 100 to 80 / 20, and more preferably 0 / 100 to 70 / 30, from the viewpoints of abrasion resistance, mechanical strength, and the like. The weight ratio of the moisture absorption regulator (D) to the hydrocarbon compound (C) in the resin composition of the present invention [(D) / (C)] is preferably 0 / 100 to 95 / 5, and more preferably 0 / 100 to 60 / 40, from the viewpoints of bleed-out resistance and the solubility of a slowly soluble drug when used as a coating layer for the drug.
[0077] The resin composition of the present invention may further contain an additive (G) as necessary within a range that does not impair the effects of the present invention. Examples of the additive (G) include a biodegradability regulator (G1), an organic filler (G2), an inorganic filler, water-absorbing resin particles, a lubricant, a plasticizer, a thixotropic agent, a foaming agent, an ultraviolet absorber, an antioxidant, a colorant, a flame retardant, a fungicide, an antisettling agent, and an antifoaming agent. The additive (G) may be used alone or in combination of two or more kinds depending on the application of the resin composition.
[0078] The resin composition of the present invention may contain a biodegradability regulator (G1) as necessary for the purpose of adjusting the biodegradability. The biodegradability regulator (G1) is an additive added to adjust the biodegradability of the resin composition of the present invention, and can be selected according to the desired biodegradability as long as it is a compound that does not fall under the above-mentioned thermoplastic resin (A), organic layered silicate (B), and hydrocarbon compound (C), and can be hydrophobic wax, hydrophobic plasticizer, olefin resin, carbodiimide compound, oxazoline compound, isocyanate compound, epoxy compound, fatty acid, amide compound, urethane compound, etc. can be used.
[0079] Examples of hydrophobic waxes include hydrocarbon waxes (such as liquid paraffin, excluding those corresponding to the above-mentioned hydrocarbon compound (C)) and metal soaps (such as aluminum stearate and calcium stearate). Examples of hydrophobic plasticizers include low molecular weight polyester plasticizers (succinic acid and ethylene glycol / propylene glycol condensates (e.g., trade name "Polysizer" series, manufactured by Dainippon Ink Co., Ltd.), etc., excluding those that fall under (A)). Examples of the carbodiimide compound include poly(4,4'-diphenylmethanecarbodiimide), poly(p-phenylenecarbodiimide), poly(m-phenylenecarbodiimide), poly(tolylcarbodiimide), poly(diisopropylphenylenecarbodiimide), poly(methyl-diisopropylphenylenecarbodiimide), and poly(triisopropylphenylenecarbodiimide). Examples of the carbodiimide compound include "Stavaxol" manufactured by Rhein Chemie and "Carbodilite" manufactured by Nisshinbo Co., Ltd., which are commercially available. Examples of the oxazoline compound include monooxazoline compounds such as 2-methyl-2-oxazoline, 2-ethyl-2-oxazoline, 2-phenyl-2-oxazoline, 2-isopropenyl-2-oxazoline, and 2,4-dimethyl-2-oxazoline; bisoxazoline compounds such as 2,2'-(1,3-phenylene)bis(2-oxazoline); and polymers having an oxazoline group in the side chain. Examples of the isocyanate compound include hexamethylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, xylylene diisocyanate, and diphenylmethane diisocyanate. Examples of epoxy compounds include ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, polybutadiene diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, cyclohexanedimethanol diglycidyl ether, hydroquinone diglycidyl ether, N-glycidyl phthalimide, hydrogenated bisphenol A diglycidyl ether, sorbitol polyglycidyl ether, and pentaerythritol. Examples of the glycidyl ether include polyglycidyl ether, glycerol polyglycidyl ether, polyglycerol polyglycidyl ether, trimethylpropane polyglycidyl ether, 2-ethylhexyl glycidyl ether, phenyl glycidyl ether, phenyl (polyethylene glycol) glycidyl ether, phenyl (polypropylene glycol) glycidyl ether, p-tert-butylphenyl glycidyl ether, diglycidyl-o-phthalate, diglycidyl terephthalate, dibromophenyl glycidyl ether, epoxidized vegetable oil, and polymers having a glycidyl group on the side chain. The fatty acid is preferably a higher fatty acid having 10 to 34 carbon atoms, and examples of the fatty acid include saturated fatty acids (capric acid, undecanoic acid, lauric acid, myristic acid, palmitic acid, margaric acid, stearic acid, arachidic acid, behenic acid, lignoceric acid, etc.) and unsaturated fatty acids (lindelic acid, petroselinic acid, oleic acid, linoleic acid, linolenic acid, arachidonic acid, montanic acid, etc.). In addition, natural oil and fat fatty acids, which are mixed fatty acids such as beef tallow fatty acid, coconut oil fatty acid, palm oil fatty acid, castor oil fatty acid, and hardened castor oil fatty acid, may be used. Examples of the amide compound include amide compounds which are reaction products of carboxylic acids having 2 to 34 carbon atoms (including the carbon of the carboxyl group) (such as behenic acid, decanoic acid, sebacic acid, azelaic acid, dodecanedioic acid, and 1,18-octadecanedicarboxylic acid) with amine compounds having 1 to 34 carbon atoms (such as hexamethylenediamine, norbornanediamine, and 1,3-bisaminomethylcyclohexane). In addition, mixtures of aliphatic amide compounds and fatty acid amides of animal and vegetable oils and fats may also be used. Examples of urethane compounds include isocyanate compounds having 4 to 22 carbon atoms (including the carbon of the isocyanate group) {cyclohexyl isocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate or a mixture thereof (TDI), hexamethylene diisocyanate (HDI), 4,4'-methylenebis(phenylisocyanate) (MDI), isophorone diisocyanate (IPDI), hydrogenated 4,4'-methylenebis(phenylisocyanate) (H12MDI), etc.} and urethane compounds which are reaction products of 1 to 50 carbon atoms with an alcohol {monohydric aliphatic alcohols such as pentyl alcohol, octyl alcohol, decyl alcohol, lauryl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, behenyl alcohol, gedelyl alcohol, and oleyl alcohol; and polyhydric aliphatic alcohols such as glycerin, ethylene glycol, propylene glycol, dodecanediol, sorbitol, and pentaerythritol}.
[0080] The resin composition of the present invention may contain an organic filler (G2) as necessary for the purpose of improving the biodegradability of the resin composition. Specific examples of the organic filler (G2) include starch such as corn starch, modified starch, agar, xanthone, and egg shell. The total content of the additives (G) is preferably 20% by weight or less, and more preferably 10% by weight or less, based on the weight of the resin composition of the present invention.
[0081] The method for producing the resin composition of the present invention is not particularly limited, but the composition can be obtained by mixing the above-mentioned (A), (B), and (C) and, if necessary, (D) and / or (G) in the presence or absence of a solvent. When mixing is performed in the presence of a solvent, the solvent is preferably an organic solvent, and examples of suitable organic solvents include chlorine-based solvents (e.g., trichloroethylene, methylene chloride, dichloroethane, tetrachloroethylene, and chloroform), ketone-based solvents (methyl ethyl ketone and methyl isobutyl ketone), aromatic solvents (benzene, toluene, xylene, and orthodichlorobenzene), amide-based solvents (N,N-dimethylacetamide and N,N-dimethylformamide), and mixtures thereof. The amount of the solvent used is not particularly limited, but 0.6 to 1.4 L, 0.7 to 1.3 L, or 0.8 to 1.2 L is used per 100 g of the total weight of (A) and (B). When mixing is performed in the absence of a solvent, for example, the above-mentioned (A) is heated to a temperature at which it melts and kneaded in a kneading device, etc. A solvent may be present when kneading in a kneading device, etc. The order in which the above-mentioned (A), (B), (C) and, if necessary, (D) and / or (G) are mixed is not particularly limited. From the viewpoint of controlling the compatibility or dispersibility of (C) in (A), it is preferable to mix (A) and (C) in the presence of (B).
[0082] When the resin composition of the present invention is obtained by mixing the above-mentioned (A), (B), and (C) and the optionally used (D) and / or (G) in the presence of a solvent, it may be in the form of a solution or dispersion obtained by mixing, or may be in the form of a solid molded product obtained by drying the solution or dispersion as necessary. The molded product may be in the form of a film or granules. To obtain a film, there is a method of casting the solution or dispersion and then drying the solvent. To obtain granules, there is a method of spray-drying the solution or dispersion by spray drying. Alternatively, as described above, the resin composition of the present invention can be obtained by mixing in the absence of a solvent, in which case the resin composition becomes, for example, a granular molded body (pellet). In order to obtain a film-shaped molded body from the granular molded body, there is a method of heat pressing the granular molded body (pellet). There is no particular restriction on the conditions for heat pressing, and the heat pressing can be performed, for example, at 180°C for 1 minute. The molded body may also be obtained by a film molding method such as T-die extrusion molding, inflation molding, and calendar molding. The molding temperature in these molding methods can be appropriately set in consideration of the properties of the thermoplastic resin (A) and the hydrocarbon compound (C) and the load of kneading, but for example, a temperature 10 to 40°C higher than the glass transition temperature of (A) is preferable.
[0083] The resin composition of the present invention combines low water vapor permeability and low moisture absorption with mechanical properties (particularly abrasion resistance), and does not cause bleed-out of the components, nor does it cause poor appearance or deterioration of water vapor permeability due to bleed-out. Therefore, by molding or coating using known methods, the composition can be used in a wide range of applications, such as packaging, cosmetics, sanitary products, agriculture, and electronic devices, making it extremely useful. In particular, it can be suitably used for applications where moisture absorption or water vapor permeability has been a problem {e.g., electronic devices (electronic substrates, etc.), coating agents for slowly soluble drugs, various agricultural materials, sanitary products, etc.}.
[0084] In the resin composition of the present invention, by using an ester group-containing thermoplastic resin (A1) as the thermoplastic resin (A), a resin composition having biodegradability can be obtained. The biodegradable resin composition of the present invention is particularly suitable for use as a material for applications requiring biodegradability in addition to low water vapor permeability, low moisture absorption, and mechanical properties. In addition to low water vapor permeability, low hygroscopicity and mechanical properties, biodegradability is required for applications such as biodegradable materials for agriculture (coatings for slowly soluble agricultural chemicals (especially agricultural chemicals sprayed on fields and paddy fields, etc.) and biodegradable agricultural materials (agricultural films, soil mulching materials, plant cultivation containers and irrigation pipes, etc.)), biodegradable materials for hygiene products (non-breathable diapers, i.e. diapers with low transpiration values similar to those for applications with backsheets of polyethylene and nonwoven polypropylene fabrics, colostomy bags and blood containers, etc.), fishing nets, bags for collecting glass cutting chips, nonwoven fabrics, and expanded products for packaging. In particular, the resin composition of the present invention can be preferably used as an agricultural biodegradable material such as a coating agent for slowly soluble agricultural chemicals.
[0085] A slowly soluble agricultural chemical is an agricultural chemical in which at least a portion of the surface of the agricultural chemical (active ingredient) is covered with one or more covering layers (coating layers) to control the release rate of the chemical, and one or more of the covering layers possessed by the slowly soluble agricultural chemical can be a coating layer made of the resin composition of the present invention.
[0086] Examples of agricultural chemicals constituting the slowly soluble agricultural chemicals include fertilizers, agricultural chemicals (fungicides, herbicides, plant growth regulators, etc.), pest control agents (repellents, insecticides, miticides, rodenticides, etc.), and the like. The fertilizer may be any known granular chemical fertilizer, including, for example, nitrogen fertilizer, phosphate fertilizer, potassium fertilizer, calcium salt, magnesium salt, iron salt, and combinations of two or more of these. Nitrogen fertilizers are fertilizers that contain nitrogen-containing compounds as their main component, and include, but are not limited to, urea, aldehyde condensed ureas such as formaldehyde condensed urea and isobutyraldehyde condensed urea, guanylurea sulfates, lime nitrogen, ammonium nitrate, ammonium sulfate, ammonium chloride, and the like. Examples of phosphate fertilizers include, but are not limited to, ammonium dihydrogen phosphate, calcium superphosphate, calcium triple superphosphate, fused phosphate fertilizer, and calcined phosphate fertilizer. Potassium fertilizers are fertilizers whose main component is potassium, and include, but are not limited to, potassium nitrate, potassium chloride, potassium sulfate, and potassium silicate. Examples of calcium salts include calcium phosphate, calcium sulfate, calcium nitrate, and calcium chloride. Examples of magnesium salts include magnesium nitrate, magnesium chloride, magnesium sulfate, and magnesium phosphate. Examples of iron salts include ferrous nitrate, ferric nitrate, ferrous phosphate, ferric phosphate, ferrous sulfate, ferric sulfate, ferrous hydrochloride, and ferric hydrochloride. Agricultural chemicals are preferably in the form of granules, in which case the weight average particle size is preferably 1 mm to 20 mm, more preferably 2 mm to 10 mm. A carrier for holding an agricultural chemical may also be used. Examples of the carrier include kaolin minerals such as kaolinite; mineral carriers such as montmorillonite, smectite, talc, rosestone, silica, hydrated calcium silicate, calcium carbonate, and zeolite; vegetable carriers such as cellulose, starch, and soybean flour; and water-soluble carriers such as lactose, sucrose, and dextrin.
[0087] The average film thickness (μm) of the coating layer made of the resin composition of the present invention in the slowly soluble agricultural chemical is preferably 10 to 150 μm, particularly preferably 10 to 103 μm, from the viewpoints of slowly soluble control, productivity and cost, and prevention of peeling of the coating layer. The average film thickness (μm) of the coating layer can be measured by the following method.
[0088] <Method for measuring the average thickness of the coating layer> The slowly soluble agricultural chemical of the present invention is cut into two parts with a razor so as to pass through the center of gravity, the cross section is photographed with a scanning electron microscope (SEM), and the thickness (μm) of the coating layer at any one point is measured. Five particles are randomly selected and cut as above, the thickness of the coating layer is measured, and the average value of the thicknesses of the coating layers of the five particles is regarded as the average film thickness (μm) of the coating layer.
[0089] In the slowly soluble agricultural chemical, the weight parts of the agricultural chemical per 100 parts by weight of the resin composition of the present invention is preferably 750 parts by weight or more and 900 parts by weight or less, and more preferably 780 parts by weight or more and 850 parts by weight or less, from the viewpoints of slowly soluble control, productivity, and cost.
[0090] The coating layer of the slowly soluble agricultural chemical and the production of the slowly soluble agricultural chemical can be carried out by combining known methods. For example, in the production of the above-mentioned resin composition, the above (A), (B), (C) and (D) and / or (G) used as necessary are mixed in the presence of a solvent to obtain a solution or dispersion, which is then sprayed or otherwise applied to the surface of the agricultural chemical using a known coating device, and then dried. When the resin composition is obtained by mixing in the absence of a solvent, the solid resin composition may be dissolved or dispersed in a solvent as necessary, and then sprayed or otherwise applied to the surface of the agricultural chemical using a known coating device, and then dried. In the production of the slowly soluble agricultural chemical, the agricultural chemical may be heated (preheated) before forming a coating layer of the slowly soluble agricultural chemical. The preheating temperature of the agricultural chemical is preferably 35 to 60°C, and may be 38 to 50°C. In the production of the slowly soluble agricultural chemical, the temperature of the inlet air when the resin composition is sprayed onto the surface of the agricultural chemical can be adjusted. The inlet air temperature is preferably 35 to 60°C, and may be 38 to 50°C. In producing a slowly soluble agricultural chemical, the pulse pressure during spraying when the resin composition is sprayed onto the surface of the agricultural chemical to form a coating layer is preferably 0.2 to 0.5 MPa. In producing the slowly soluble agricultural agent, the drying temperature after spraying the resin composition onto the surface of the agricultural agent is preferably 10 to 120°C.
[0091] The resin composition of the present invention can also be preferably used as a biodegradable agricultural material such as an agricultural film, a soil mulching material, a plant cultivation container, an irrigation pipe, etc. Examples of agricultural films using the resin composition of the present invention include those molded to a thickness of 0.01 mm to 1 mm by a method such as a melt extrusion molding method (inflation method).
[0092] The present specification discloses the following:
[0093] The present disclosure (I) is a resin composition containing a thermoplastic resin (A), an organically modified layered silicate (B), and a hydrocarbon compound (C) having 20 or more carbon atoms, and the resin composition satisfies all of the following (1) to (3): (1) The content of (A) in the resin composition is 15% by weight or more and 90% by weight or less based on the total weight of (A), (B) and (C). (2) The solubility parameter of (A) is 9.0 to 12.5 (cal / cm 3 ) 1 / 2 It is. (3) The melting point of (C) is 35°C or higher and 180°C or lower.
[0094] The present disclosure (II) is the resin composition according to the present disclosure (I), wherein the organically modified layered silicate (B) is a layered silicate having an organic compound between layers, a layered silicate having an organic group having 6 or more carbon atoms on its surface, or a layered silicate having an organic compound between layers and having an organic group having 6 or more carbon atoms on its surface.
[0095] The present disclosure (III) is a resin composition according to the present disclosure (I) or (II), in which the swelling power of the organically modified layered silicate (B) in chloroform, measured by replacing water with chloroform in the standard test method for swelling test of bentonite (powder) (JBAS104:77) of the Japan Bentonite Industry Association, is 70 mL / 2 g or less.
[0096] The present disclosure (IV) relates to a thermoplastic resin (A) having an ester group of 0.1 g / g or more based on the weight of the thermoplastic resin (A) and a solubility parameter of 9.1 to 11.5 (cal / cm 3 ) 1 / 2 The resin composition according to any one of the present disclosures (I) to (III) is an ester group-containing thermoplastic resin (A1) represented by the formula (I) below.
[0097] The present disclosure (V) relates to a thermoplastic resin (A) having an amide group and / or an imide group, the weight ratio of the amide group and the imide group being 0.1 g / g or less based on the weight of the (A), and the solubility parameter being 9.1 to 11.5 (cal / cm 3 ) 1 / 2 The resin composition according to any one of the present disclosures (I) to (IV).
[0098] The present disclosure (VI) is a resin composition in any combination with any of the present disclosures (I) to (V), in which the weight ratio of the organically modified layered silicate (B) to the hydrocarbon compound (C) [(B) / (C)] is 20 / 80 to 80 / 20.
[0099] The present disclosure (VII) is a resin composition having a content weight ratio [(A) / (C)] of the thermoplastic resin (A) to the hydrocarbon compound (C) of 40 / 60 to 95 / 5, and is any combination with any of the present disclosures (I) to (VI).
[0100] The present disclosure (VIII) is a resin composition in which the melting point of the hydrocarbon compound (C) is 100° C. or lower, and which is any combination with any of the present disclosures (I) to (VII).
[0101] The present disclosure (IX) is a resin composition in which the molecular weight of the hydrocarbon compound (C) is 500 or less, and which is any combination with any of the present disclosures (I) to (VIII).
[0102] The present disclosure (X) is a resin composition according to any one of the present disclosures (I) to (IX) for use as an agricultural biodegradable material. EXAMPLES
[0103] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. In the following, unless otherwise specified, parts indicate parts by weight.
[0104] The raw materials used in the examples and comparative examples are as follows. <Thermoplastic resin (A)> (A-1): Polybutylene succinate adipate ["BioPBS FD92", manufactured by Mitsubishi Chemical Corporation, SP value 10.7 (cal / cm 3 ) 1 / 2 , glass transition temperature (Tg) = -40°C, ester group concentration 0.45g / g] (A-2): Polybutylene succinate ["BioPBS FZ91", manufactured by Mitsubishi Chemical Corporation, SP value 10.9 (cal / cm 3 ) 1 / 2 , glass transition temperature -22℃, ester group concentration 0.50g / g] (A-3): Polybutylene succinate [Bionolle 1001, Showa Polymer Co., Ltd., SP value 10.9 (cal / cm 3)1 / 2 , glass transition temperature -32℃, ester group concentration 0.50g / g] (A-4): Polybutylene adipate terephthalate ["ecoflex (registered trademark) F Blend C1200", manufactured by BASF, SP value 11.1 (cal / cm 3 ) 1 / 2 , Tg = -45°C, ester group concentration 0.42g / g] (A-5): Polycaprolactone ["CAPA6500", manufactured by Ingevity, SP value 10.2 (cal / cm 3 ) 1 / 2 , Tg = -60°C, ester group concentration 0.38g / g] (A-6): Polylactic acid [Luminy (registered trademark) L130”, manufactured by TotalEnergies Corbion, SP value 11.1 (cal / cm 3 ) 1 / 2 , Tg = 60°C, ester group concentration 0.60g / g] (A-7): Hydrogenated rosin ester ["Ester Gum-H", manufactured by Arakawa Chemical Industries, Ltd., SP value 9.1 (cal / cm 3 ) 1 / 2 , Tg = 10°C, ester group concentration 0.13g / g] (A-8): Cellulose acetate ["XDN195", Daicel Miraizu Co., Ltd., SP value 11.2 (cal / cm 3 ) 1 / 2 , Tg = 110°C, ester group concentration 0.15g / g] (A-9): Polyester-based thermoplastic polyurethane resin (produced in Production Example 1) [SP value 10.0 (cal / cm 3 ) 1 / 2 , Tg = -30°C, ester group concentration 0.17g / g] (A-10): Semi-aromatic polyamide resin (produced in Production Example 2) [SP value 12.3 (cal / cm 3 ) 1 / 2 , Tg = 45°C, ester group concentration 0.18g / g, total concentration of amide groups and imide groups 0.03g / g, total concentration of ester groups, amide groups and imide groups 0.21g / g] (A-11): Polybutylene succinate terephthalate (produced in Production Example 3) [SP value 10.9 (cal / cm 3 ) 1 / 2 , Tg = -30°C, ester group concentration 0.52 g / g, relative crystallinity 2%] (A-12): Polyethylene succinate (produced in Production Example 8) [SP value 11.5 (cal / cm 3 ) 1 / 2 , Tg = -35°C, ester group concentration 0.61g / g] (A-13): Aliphatic polyester consisting of succinic acid / sebacic acid / ethylene glycol (produced in Production Example 9) [SP value 11.0 (cal / cm 3 ) 1 / 2 , Tg = -40°C, ester group concentration 0.53g / g] (A-14): Aliphatic polyester consisting of succinic acid / dodecanedioic acid / ethylene glycol (produced in Production Example 10) [SP value 10.9 (cal / cm 3 ) 1 / 2 , Tg = -38°C, ester group concentration 0.51g / g]
[0105] <Organic Layered Silicate (B)> (B-1): Organo-bentonite having an organic compound between layers ["Kunibis (registered trademark) 217", manufactured by Kunimine Kogyo Co., Ltd., median diameter 10 to 20 μm, interlayer organic cation: dimethyl distearyl ammonium (carbon number 38), swelling power in chloroform: 17 mL / 2 g, modification rate 46%] (B-2): Organo-bentonite having an organic compound between layers ["Kunibis (registered trademark) 127", manufactured by Kunimine Kogyo Co., Ltd., median diameter 10 to 20 μm, interlayer organic cation: benzyl dimethyl stearyl ammonium (carbon number 27), swelling power in chloroform: 44 mL / 2 g, modification rate 36%] (B-3): Organo-mica having an organic compound between layers ["Somasif (registered trademark) MAE", manufactured by Katakura Co-op Agri Co., Ltd., median diameter 10 to 20 μm, interlayer organic cation: dimethyl distearyl ammonium (carbon number 27), swelling power in chloroform: 13 mL / 2 g, modification rate 30%] (B-4): Organo-talc having an organic group on the surface (produced in Production Example 4) [surface modification group (organic group derived from coupling agent): 3-methacryloxypropyldimethoxysilane (carbon number: 11), median diameter: 30 μm, swelling power in chloroform: 2 mL / 2 g, modification rate: 40%] (B-5): Organo-mica having organic groups on the surface ["SUZORITE (registered trademark) 150-PO", median diameter 40 μm, manufactured by Imerys, surface treatment agent: γ-glycidoxypropyl-trimethoxysilane, surface modification group (organic group derived from coupling agent): γ-glycidoxypropyl-dimethoxysilane (carbon number 8), swelling power in chloroform: 15 mL / 2 g, modification rate 30%]] (B-6): Organo-bentonite having organic groups on the surface and organic compounds between layers (produced in Production Example 5) [Interlayer organic cation: dimethyl distearyl ammonium (carbon number: 38), surface modification group (organic group derived from coupling agent): dimethyl methoxy silane (carbon number: 3), swelling power in chloroform: 40 mL / 2 g, median diameter: 10 to 20 μm, modification rate: 50%] (B-7): Organo-bentonite having an organic group compound between layers (produced in Production Example 6) [Interlayer organic cation: decylammonium ion (carbon number: 10), swelling power in chloroform: 12 mL / 2 g, median diameter: 10 to 20 μm, modification rate: 15%] (B-8): Organo-bentonite having an organic compound between layers (produced in Production Example 7) [Interlayer compound: polyether compound (carbon number: 12), swelling power in chloroform: 20 mL / 2 g, median diameter: 20 μm, modification rate: 25%] (B-9): Organo-bentonite with organic compounds between layers ["Esben NX", manufactured by Hojun Co., Ltd., particle size 10-20 μm, interlayer organic cation: dimethyl distearyl ammonium (carbon number: 38), swelling power in chloroform 21 mL / 2 g, median diameter 20 μm, modification rate 42%]] <Layered silicate for comparison (comparison B)> (Comparison B-1): Montmorillonite ["Kunipia (registered trademark)-F", manufactured by Kunimine Kogyo Co., Ltd., median diameter 10 to 20 μm, interlayer metal ion: sodium, swelling power in chloroform: cannot be measured because it floats on the surface of chloroform and does not swell]
[0106] <Hydrocarbon compounds with 20 or more carbon atoms (C)> (C-1): Paraffin wax ["Paraffin (mp. 42-44°C)", Fujifilm Wako Pure Chemical Industries, Ltd., melting point 43°C, molecular weight 300] (C-2): Paraffin wax ["PARAFFIN WAX-155", manufactured by Nippon Seiro Co., Ltd., melting point 69°C, molecular weight 500] (C-3): Paraffin wax ["HNP-9", Nippon Seiro Co., Ltd., melting point 75°C, molecular weight 500] (C-4): Microcrystalline wax ["Hi-Mic-1045", manufactured by Nippon Seiro Co., Ltd., melting point 72°C, molecular weight 450] (C-5): Microcrystalline wax ["Hi-Mic-1090", Nippon Seiro Co., Ltd., melting point 88°C, molecular weight 900] (C-6): Polyethylene wax ["SANWAX (registered trademark) 151-P", manufactured by Sanyo Chemical Industries, Ltd., melting point 102°C, number average molecular weight 2000, weight average molecular weight 12500] (C-7): Polyethylene ["UBE Polyethylene (registered trademark) J5019", manufactured by Ube Maruzen Polyethylene Co., Ltd., melting point 108°C, weight average molecular weight > 100,000] (C-8): Polyethylene ["Novatec (registered trademark) PP BC08F", manufactured by Japan Polypropylene Co., Ltd., melting point 165°C, weight average molecular weight > 100,000] <Comparative compound (Comparative C)> (Comparison C-1): Liquid paraffin ["Liquid paraffin (Wako Grade 1)", Fujifilm Wako Pure Chemical Industries, Ltd., melting point below 20°C, molecular weight 200]
[0107] <Moisture absorption regulator (D)> (D-1): Rice wax ["Rice Bran Wax XECO-0002B", manufactured by Nippon Seiro Co., Ltd.] (D-2): Carnauba wax [Refined carnauba wax No. 1 powder, manufactured by Nippon Wax Co., Ltd.] (D-3): Sunflower wax [manufactured by Yamakei Industry Co., Ltd.] (D-4): Stearyl stearate ["Unistar M-9676", NOF Corporation] <Additives (G)> (G-1): Carbodiimide compound ["Carbodilite (registered trademark) HMV-15CA", manufactured by Nisshinbo Chemical Inc.] (G-2): Castor oil fatty acid [manufactured by Kokura Synthetic Industries Co., Ltd.] (G-3): Eggshell [GT-26 [average particle size 30 μm (manufactured by Green Techno 21 Co., Ltd.)]
[0108] Production Example 1 [Production of (A-9)] 1000 parts of poly(1,4-butylene adipate) (molecular weight 1000) and 150 parts of 1,4-butanediol were mixed at a temperature of 80°C. 670 parts of diphenylmethane diisocyanate (MDI) were added thereto, and the mixture was stirred and mixed while controlling the temperature so that the solution temperature was 110°C. When the temperature reached 110°C, the stirring was stopped, the temperature was controlled to 125°C, and the mixture was left to stand for 10 minutes. Thereafter, the mixture was left to stand in a forward air dryer at 80°C for 15 minutes to obtain a polyester-based thermoplastic polyurethane resin (A-9).
[0109] Production Example 2 [Production of (A-10)] 113 parts of ε-caprolactam, 27 parts of sodium 3-isophthalate, and 30 parts of water were added and mixed under an inert atmosphere at 220°C to form a solution, and then 105 parts of bisphenol A ethylene oxide adduct having a number average molecular weight of 1000 and 0.3 parts of tetrabutyl titanate were added and copolycondensation was carried out at 260°C under reduced pressure to obtain a semi-aromatic polyamide resin (A-10).
[0110] Production Example 3 [Production of (A-11)] 49.2 parts of 1,4-butanediol, 28.1 parts of succinic acid, and 46.2 parts of dimethyl terephthalate were charged into a glass polymerization tube equipped with a stirring blade, a vacuum port, and a nitrogen inlet, and the system was substituted with nitrogen by vacuum replacement to create a nitrogen atmosphere. Next, the system was heated to 185°C while stirring, and held for 30 minutes. After that, the temperature was raised to 220°C over 1 hour and 30 minutes, the water generated by the reaction was distilled off, and an esterification reaction was carried out. Here, 0.071 g of tetrabutyl titanate and 0.045 g of magnesium acetate tetrahydrate were dissolved in 1,4-butanediol as a catalyst and added to the system. Next, the temperature was raised to 230°C over 1 hour, and at the same time, the pressure was gradually reduced to 0.5 mmHg over 1 hour and 30 minutes. After reaching 230°C, the reaction was carried out for 4 hours to obtain polybutylene succinate terephthalate (A-11).
[0111] Production Example 4 [Production of (B-4)] A glass container containing 1000 parts of methanol and 100 parts of talc ["Crown Talc PP", Matsumura Sangyo Co., Ltd.] was placed in an ultrasonic cleaner at 25°C for 30 minutes, and the talc was dispersed in the methanol to obtain a methanol dispersion of talc. A mixture of 2 parts of 3-methacryloxypropyltrimethoxysilane ["KBM-503", Shin-Etsu Chemical Co., Ltd.] and 10 parts of toluene was dropped into the methanol dispersion of talc under stirring, and then stirred for 1 hour. Next, the mixture was thoroughly air-dried at room temperature, and then heated in a thermostatic bath at 120°C for 2 hours to obtain an organic talc (B-4) having an organic group on the surface.
[0112] Production Example 5 [Production of (B-6)] 100 parts of organic bentonite having an organic compound between layers ["Kunibis (registered trademark) 217", Kunimine Kogyo Co., Ltd.], 132 parts of trimethylmethoxysilane, and 14 parts of acetic acid were added to 500 parts of toluene and mixed, and then heated at 55°C for 8 hours. The toluene was distilled off under reduced pressure, and the obtained solid was washed three times with ethyl acetate, and then freeze-dried using a small freeze dryer ["FDS-2000", EYELA Co., Ltd.] under conditions of a trap cooling temperature of -80°C, a vacuum pump of 110 L / min, and a drying time of 24 hours, thereby obtaining an organic bentonite (B-6) having an organic compound between layers and an organic group on the surface.
[0113] Production Example 6 [Production of (B-7)] 80 g of montmorillonite ["Kunipia (registered trademark)-F", Kunimine Kogyo Co., Ltd.] was dispersed in 5000 mL of water at 80°C to obtain an aqueous dispersion of montmorillonite. 21.1 g of decylamine and 4.2 g of concentrated hydrochloric acid were dissolved in 2000 mL of water at 80°C, and this solution was added to the aqueous dispersion of montmorillonite to obtain a precipitate. The precipitate was collected by filtration using a membrane filter (pore size 0.8 μm), washed three times with water at 80°C, and then freeze-dried using a small freeze-dryer ["FDS-2000", EYELA Co., Ltd.] under conditions of a trap cooling temperature of -80°C, a vacuum pump of 110 L / min, and a drying time of 24 hours, thereby obtaining an organically modified montmorillonite (B-7) having an organic compound between layers.
[0114] Production Example 7 [Production of (B-8)] 80 g of mica ("Somasif (registered trademark) ME100", manufactured by Katakura Co-op Agri Co., Ltd.) was dispersed in 5000 ml of water at 80°C. Polyethylene glycol ("PEG400", number average molecular weight 400, manufactured by Sanyo Chemical Industries, Ltd.) was added to this solution and mixed for 30 minutes to obtain a precipitate. This precipitate was collected by membrane filter filtration, washed three times with water at 80°C, and freeze-dried using a small freeze dryer ("FDS-2000", manufactured by EYELA) under conditions of a trap cooling temperature of -80°C, a vacuum pump of 110 L / min, and a drying time of 24 hours, thereby obtaining an organically modified mica (B-8) having an organic compound (polyether compound) between layers.
[0115] Production Example 8 [Production of (A-12)] In a four-neck flask equipped with a reflux condenser, a thermometer, a nitrogen inlet tube, and a stirrer, 38.2 parts of ethylene glycol, 72.6 parts of succinic acid, and 1.5 parts of titanium dihydroxybis(triethanolamine) as a condensation catalyst were charged, and nitrogen gas was passed through under normal pressure, and esterification was performed while distilling off water at 190°C until the acid value was 10 or less. Subsequently, the water generated was distilled off under reduced pressure of 0.5 to 2.5 kPa at 190°C, and the reaction was continued until the acid value was less than 3.0, to obtain an aliphatic polyester resin (A-12).
[0116] Production Example 9 [Production of (A-13)] In a four-neck flask equipped with a reflux condenser, a thermometer, a nitrogen inlet tube, and a stirrer, 29.6 parts of ethylene glycol, 56.1 parts of succinic acid, 32.1 parts of sebacic acid, and 1.5 parts of titanium dihydroxybis(triethanolamine) as a condensation catalyst were charged, and nitrogen gas was passed through under normal pressure, and while distilling off water at 190°C, esterification was performed until the acid value was 10 or less, and then the water generated was distilled off under a reduced pressure of 0.5 to 2.5 kPa at 190°C, and the reaction was continued until the acid value was less than 3.0, to obtain an aliphatic polyester resin (A-13).
[0117] Production Example 10 [Production of (A-14)] In a four-neck flask equipped with a reflux condenser, a thermometer, a nitrogen inlet tube, and a stirrer, 32.6 parts of ethylene glycol, 46.4 parts of succinic acid, 30.1 parts of dodecanedioic acid, and 1.5 parts of titanium dihydroxybis(triethanolamine) as a condensation catalyst were charged, and nitrogen gas was passed through under normal pressure, and while distilling off water at 190°C, esterification was performed until the acid value was 10 or less, and then the water generated was distilled off under a reduced pressure of 0.5 to 2.5 kPa at 190°C, and the reaction was continued until the acid value was less than 3.0, to obtain an aliphatic polyester resin (A-14).
[0118] Example 1 [Production of cast film-like resin composition (X-1)] 30 parts of thermoplastic resin (A-1), 40 parts of organic layered silicate (B-1), and 30 parts of hydrocarbon compound (C-1) were dissolved or dispersed in 2 L of trichloroethylene using a stirrer to a total of 100 g. Then, 300 μm thick masking tape was applied to both ends of the upper surface of a 20 cm x 20 cm x 0.5 cm glass plate, and 8 mL of the above solution was poured between them, leveled using a glass rod, and heated air was applied in a forward wind dryer for 1 hour so that the surface temperature reached 40°C to volatilize trichloroethylene. This operation was repeated until the film thickness was 100 μm, and a cast film-like resin composition (X-1) was obtained.
[0119] Examples 2 to 31 and Comparative Examples 1 to 4 [Production of cast film-like resin compositions (X-2) to (X-31) and comparative resin compositions (Comparative X-1) to (Comparative X-4)] Cast film-like resin compositions (X-2) to (X-31) and comparative resin compositions (Comparative X-1) to (Comparative X-4) were obtained in the same manner as in Example 1, except that the components shown in the composition (parts) of the resin compositions in Tables 1 and 2 were used.
[0120] The content of (A) based on the total weight of (A), (B) and (C) in each cast film-like resin composition (X) and (ratio X) obtained in the examples and comparative examples [(A) / (A)+(B)+(C)], the weight ratio [(B) / (C)], the content of (A) relative to the total weight of (A) and (B) [(A) / {(A)+(B)}] weight ratio [(A) / (C)], the solubility parameter (SP value) of (A), the ester group concentration (g / g) of (A), the total concentration (g / g) of amide groups and imide groups of (A), the total concentration (g / g) of ester groups, amide groups and imide groups of (A), the swelling power of (B) in chloroform, the state of (C) in (A) in each (X) and (ratio X) measured by the above method, the melting point of (C), and the molecular weight of (C) are shown in Tables 1 to 2. Moreover, the biodegradability (degree of disintegration), moisture permeability and moisture absorption (water absorption rate) of each (X) and (ratio X) were measured and evaluated by the following methods. The results are shown in Tables 1 and 2. However, in Comparative Example 4 (Comparative Example X-4), (Comparative Example B-1) floated to the surface during film formation, making it impossible to form a uniform cast film, so the biodegradability (disintegration degree), moisture permeability, and moisture absorption (water absorption rate) were not evaluated. In addition, since (Comparative Example 1) (Comparative Example X-1) did not contain (C), a "-" was entered in the column for the presence state of (C) in (A), and since most of the comparative compound (Comparative Example C) in (Comparative Example 3) (Comparative Example X-3) bled out onto the surface of the resin composition, and the presence state of (C) in (A) could not be confirmed, a "-" was entered in the column for the presence state of (C) in (A). In addition, in the state of existence of (C) in (A), when the discontinuous phase (C) is present in the continuous phase (A) in the form of islands in a sea (i.e., a sea-island structure), it is described as "particulate", and when both (A) and (C) form continuous phases (i.e., a bicontinuous structure), it is described as "layered". The maximum value of the short side of the minimum circumscribing rectangle of (C) in the case of an island-in-a-sea structure and the layer width in the case of a bicontinuous structure are described in the "Phase separation size" column. The biodegradability (degree of disintegration), moisture permeability and moisture absorption (water absorption rate) are evaluated for the cast film-like resin composition. The biodegradability (degree of disintegration) of the cast film-like resin composition is almost directly reflected in the biodegradability of the molded film-like resin composition and the coating layer of the slowly soluble agricultural chemical.
[0121] [Table 1]
[0122] [Table 2]
[0123] (1) Biodegradability (degradation) of the resin composition Each cast film-like resin composition obtained in the Examples and Comparative Examples was cut to a size of 15 mm x 15 mm x film thickness, and then the disintegration degree (%) was measured according to JIS K 6954. The disintegration degree (weight loss rate) (%) after 30 days at 60°C was evaluated according to the following criteria. <Evaluation criteria> ☆:Over 90% ◎: 80% or more but less than 90% ○: 60% or more but less than 80% △: 10% to less than 60% ×: Less than 10%
[0124] (2) Moisture permeability Each cast film-like resin composition obtained in the Examples and Comparative Examples was used as a measurement sample, and the moisture permeability (unit: g / m2) was measured according to the moisture permeability cup method (JIS Z0208-1976, condition A). 2 The thermal shock resistance was measured for 24 hours and evaluated according to the following criteria. <Evaluation criteria> ◎: 15g / m 2 ·24 hours or less 〇:15g / m 2 25g / m over 24hr 2 ·24 hours or less △:25g / m 2 40g / m over 24hr 2 ·24 hours or less ×:40g / m 2 ·Over 24 hours
[0125] (3) Hygroscopicity (water absorption rate) Each cast film-like resin composition obtained in the Examples and Comparative Examples was cut to a size of 5 cm x 5 cm x film thickness to obtain a test piece. The test piece was dried at 80°C for 1 hour, and then its weight (W1) was measured. The test piece was then immersed in water at 25°C, left in an atmosphere at 25°C for 24 hours, removed, carefully wiped off the moisture with a rag, and its weight (W2) was measured. The water absorption rate (wt%) was calculated using the following formula and evaluated according to the following criteria. Water absorption rate (weight%)=100×(W2-W1) / W1 <Evaluation criteria> ◎: 5% by weight or less 〇: More than 5% by weight and less than 10% by weight △: More than 10% by weight and less than 15% by weight ×: More than 15% by weight
[0126] Example 35 [Production of a molded film-like resin composition (X-35)] 30 parts of thermoplastic resin (A-1), 40 parts of organic layered silicate (B-1), and 30 parts of hydrocarbon compound (C-1) were premixed in a disposable cup, then charged into a Labo Plastomill whose temperature was adjusted to the temperature (molding temperature) shown in Table 2, and mixed at 60 rpm for 10 minutes to obtain a kneaded product. This kneaded product was hot-pressed in a pressure molding machine whose temperature was adjusted to the molding temperature (°C) shown in Table 3 under conditions of 3 kPa and 1 minute to obtain a molded film-like resin composition (X-35) having a thickness of 2 mm.
[0127] Examples 36 to 65 and Comparative Examples 11 to 14 [Production of molded film-like resin compositions (X-36) to (X-65) and comparative resin compositions (Comparative X-11) to (Comparative X-14)] A resin composition in the form of a molded film having a thickness of 2 mm was obtained in the same manner as in Example 35, except that the components shown in the composition (parts) of the resin composition in Tables 3 and 4 were used and the molding temperature (°C) was set to the temperatures shown in Tables 3 and 4.
[0128] The content of (A) based on the total weight of (A), (B) and (C) in each molded film-like resin composition (X) and (ratio X) obtained in the examples and comparative examples [(A) / (A)+(B)+(C)], the weight ratio [(B) / (C)], the content of (A) relative to the total weight of (A) and (B) [(A) / {(A)+(B)}] weight ratio [(A) / (C)], the solubility parameter (SP value) of (A), the ester group concentration (g / g) of (A), the total concentration (g / g) of amide groups and imide groups of (A), the total concentration (g / g) of ester groups, amide groups and imide groups of (A), the swelling power of (B) in chloroform, the state of (C) in (A) in each (X) and (ratio X) measured by the above method, the melting point of (C), and the molecular weight of (C) are shown in Tables 3 to 4. Moreover, the bleed-out resistance and abrasion resistance of each (X) and (Ratio X) were measured and evaluated by the following methods, and the results are shown in Tables 3 and 4. In addition, in the state of existence of (C) in (A), when the discontinuous phase (C) is present in the continuous phase (A) in the form of islands in a sea (i.e., a sea-island structure), it is described as "particulate", and when both (A) and (C) form continuous phases (i.e., a bicontinuous structure), it is described as "layered". The maximum value of the short side of the minimum circumscribing rectangle of (C) in the case of an island-in-a-sea structure and the layer width in the case of a bicontinuous structure are described in the "Phase separation size" column. In addition, since Comparative Example 11 (Comparative Example X-11) does not contain (C), "-" is entered in the columns for the presence state of (C) in (A) and bleed-out resistance, and in Comparative Example 13 (Comparative Example X-13), many of the comparative compounds (Comparative Example C) bled out onto the surface of the resin composition, making it impossible to confirm the presence state of (C) in (A), so "-" is entered in the presence state of (C) in (A).
[0129] [Table 3]
[0130] [Table 4]
[0131] (4) Bleed-out properties The molded film-like resin composition obtained in each Example and Comparative Example was sheared to a thickness of 30 mm × 30 mm × film thickness to prepare a test piece, which was then stored for 7 days under conditions of a temperature of 60° C. and a humidity of 100% RH. After storage, the surface of the test piece was observed with an optical microscope (magnification of 500 times) and evaluated according to the following criteria. <Evaluation criteria> ○: No bleed-out observed ×: Bleeding out is observed
[0132] (5) Abrasion resistance The molded film-like resin composition obtained in each Example and Comparative Example was cut into a disk shape with a diameter of about 100 mm to prepare a test piece, and an abrasion test was carried out using a Taber abrasion tester under the following abrasion conditions. The moisture permeability (unit: g / m2) of the test piece before and after the abrasion test was2 The moisture permeability (ΔA) (%) before and after the abrasion test was calculated, and the abrasion resistance was evaluated according to the following criteria. ΔA(%)=100×[{Moisture permeability after abrasion test(g / m 2 24hr)-Moisture permeability before abrasion test (g / m 2 24hr) / Moisture permeability before abrasion test (g / m 2 24hrs) <Wear conditions> Load: 2.45N Rotation speed: 60 rpm Wear wheel: CS-10 Test count: 1000 consecutive times <Evaluation criteria> ◎: ΔA is 10% or less ○: ΔA is more than 10% and less than 30% △: ΔA is more than 30% and less than 50% ×: ΔA is more than 50%
[0133] Example 66 [Preparation of slowly soluble agricultural chemical (Z-1)] 100 g of the resin composition (X-1) was dissolved or dispersed in about 1 L of trichloroethylene. Then, using a fluidized bed coating device [Spiraflow SFC-LABO (manufactured by Freund)], 800 g of urea fertilizer (N-1) [particle size 2.0-4.0 mm, average particle size 3.3 mm, circularity coefficient 0.9] was sprayed and dried under the following conditions to obtain a slowly soluble agricultural chemical (Z-1) having a coating layer made of the resin composition (X-1). <Condition> Fertilizer preheating temperature: 40℃ Supply air temperature: 50℃ Pulse pressure: 0.3MPa
[0134] Examples 67 to 96 and Comparative Examples 21 to 24 [Production of slowly soluble agricultural chemicals (Z-2) to (Z-31) and comparative slowly soluble agricultural chemicals (Comparative Z-1) to (Comparative Z-4)] Slowly soluble agricultural chemicals (Z-2) to (Z-31) and comparative slowly soluble agricultural chemicals (comparative Z-1) to (comparative Z-4) were obtained in the same manner as in Example 66, except that 100 g of resin composition (X) or comparative resin composition (comparative X) shown in Tables 5 to 6 was used instead of resin composition (X-1), and the weight (g) of urea fertilizer (N-1) was changed to the weight (g) shown in Tables 5 to 6, respectively. However, in Comparative Example 24, the film forming property was poor, and a uniform coating layer could not be formed on the surface of the urea fertilizer.
[0135] [Table 5]
[0136] [Table 6]
[0137] For each of the slowly soluble agricultural chemicals obtained in the Examples and Comparative Examples, the slowly soluble properties of the chemicals (initial dissolution rate and number of days for 80% dissolution) and the abrasion resistance of the coating layer were evaluated by the methods described below. The results are shown in Tables 5 to 6. As for Comparative Example 24, since a uniform coating layer could not be formed as described above, the gradual solubility of the drug and the abrasion resistance of the coating layer were not evaluated, and it was recorded as "unevaluable."
[0138] (5) Slow dissolution of drugs 50 g of each slowly soluble agricultural chemical (Z) or (comparison Z) and 100 g of ion-exchanged water were added to a sealable wide-mouth glass sample bottle and stored in a thermostatic chamber at 25°C. Starting from the fifth day after the start of storage, the liquid was stirred and 1 g was sampled every other day, and the urea (N-1) contained in the sampled liquid was quantified using a liquid chromatography mass spectrometer (LC / MS). <Measurement conditions> Equipment: LCMS-8030 (Shimadzu Corporation) Column: Inert Sustain C18 (silica gel particle diameter 2 μm, inner diameter 2.1 mm, length 100 mm) Column temperature: 40℃ Mobile phase A: 10 mM ammonium acetate aqueous solution / methanol = 80 / 20 Mobile phase B: Methanol Flow rate: 0.2ml / min
[0139] <Evaluation method> [1] Initial dissolution rate (%): The dissolution rate after 5 days of storage in a thermostatic chamber at 25°C The initial dissolution rate (%) was calculated using the following formula and evaluated according to the following criteria. Initial dissolution rate (%) = {weight fraction of urea (N-1) in the sampled solution after storage for 5 days in a thermostatic chamber at 25°C / weight fraction in the sampled solution when the entire amount of urea (N-1) contained in the slowly soluble agricultural chemical (Z) is dissolved} x 100 [Evaluation Criteria] ◎: Less than 5% 〇: More than 5% but less than 20% △: More than 20% but less than 50% ×: More than 50%
[0140] [2] 80% dissolution time (days): The number of days until 80% by weight of the urea (N-1) contained in the slowly soluble agricultural chemical (Z) or (comparison Z) before the test was dissolved was evaluated according to the following criteria. [Evaluation Criteria] ☆: 90 days or more ◎: 60 days or more and 89 days or less 〇: 40 days or more and 59 days or less △: 30 days or more and 39 days or less ×: 29 days or less
[0141] (6) Abrasion resistance of the coating layer An abrasion test was conducted in which 50 g of each slowly soluble agricultural chemical (Z) was dropped 10 times from a height of 1 m through a vertically erected rigid polyvinyl chloride pipe (PVC pipe) [nominal diameter 13, length 1 m, outer diameter 18 mm] onto the bottom of a stainless steel container. The initial dissolution rate (%) of the (Z) after the abrasion test was measured and calculated in the same manner as in (5)[1] above. If cracks or chips occur in the coating layer due to abrasion, the initial dissolution rate will be greater than that of (5)[1]. Therefore, the difference in the initial dissolution rate before and after spraying, ΔB (%), was calculated using the following formula, and the abrasion resistance was evaluated according to the following criteria. ΔB(%)={initial dissolution rate (%) of (Z) after spraying}-{initial dissolution rate (%) of (Z) before spraying (above (5)[1])} [Evaluation Criteria] ◎: Less than 5% ○: More than 5% and less than 10% △: More than 10% but less than 20% ×: More than 20% [Industrial Applicability]
[0142] The resin composition of the present invention combines low water vapor permeability and low moisture absorption with mechanical properties (particularly abrasion resistance), and does not cause bleed-out of the components, nor does it cause poor appearance or deterioration of water vapor permeability due to bleed-out. Therefore, by molding or coating using known methods, the composition can be used in a wide range of applications, such as packaging, cosmetics, sanitary products, agriculture, and electronic devices, making it extremely useful. In particular, it can be suitably used for applications where moisture absorption or water vapor permeability has been a problem {e.g., electronic devices (electronic substrates, etc.), coating agents for slowly soluble drugs, various agricultural materials, sanitary products, etc.}. In addition, the resin composition of the present invention using a thermoplastic resin having an ester group such as the ester group-containing thermoplastic resin (A1) as the thermoplastic resin (A) can be particularly suitably used as a material for applications requiring low water vapor permeability, low hygroscopicity, mechanical properties, and biodegradability. Applications requiring low water vapor permeability, low hygroscopicity, mechanical properties, and biodegradability include agricultural biodegradable materials {slowly soluble agricultural chemicals (especially coating agents for agricultural chemicals sprayed on fields and paddy fields) and biodegradable agricultural materials (agricultural films, soil mulching materials, plant cultivation containers and irrigation pipes, etc.)}, biodegradable materials for sanitary products {non-breathable diapers, i.e., diapers with low transpiration values similar to those for applications having a backsheet of polyethylene and nonwoven polypropylene fabric, colostomy bags, blood containers, etc.}, fishing nets, bags for collecting glass cutting chips, nonwoven fabrics, and inflated products for packaging.
Claims
1. The resin composition contains a thermoplastic resin (A), an organically modified layered silicate (B), and a hydrocarbon compound (C) having 20 or more carbon atoms, and satisfies all of the following (1) to (3): (1) The content of (A) in the resin composition is 15% by weight or more and 90% by weight or less based on the total weight of (A), (B) and (C). (2) The solubility parameter of (A) is 9.0 to 12.5 (cal / cm 3 ) 1/2 It is. (3) The melting point of (C) is 35° C. or higher and 180° C. or lower.
2. The resin composition according to claim 1, wherein the organically modified layered silicate (B) is a layered silicate having an organic compound between layers, a layered silicate having an organic group having 6 or more carbon atoms on its surface, or a layered silicate having an organic compound between layers and an organic group having 6 or more carbon atoms on its surface.
3. The resin composition according to claim 1, wherein the swelling power of the organically modified layered silicate (B) in chloroform, as measured according to the standard test method for swelling of bentonite (powder) (JBAS104:77) of the Japan Bentonite Industry Association, is 70 mL / 2 g or less, except that water is replaced with chloroform.
4. The thermoplastic resin (A) has an ester group of 0.1 g / g or more based on the weight of the thermoplastic resin (A) and has a solubility parameter of 9.1 to 11.5 (cal / cm 3 ) 1/2 The resin composition according to claim 1 ,
5. The thermoplastic resin (A) has an amide group and / or an imide group, the weight ratio of the amide group and the imide group is 1 g / g or less based on the weight of the thermoplastic resin (A), and the solubility parameter is 9.1 to 11.5 (cal / cm 3 ) 1/2 The resin composition according to claim 1 ,
6. 2. The resin composition according to claim 1, wherein the weight ratio of the organically modified layered silicate (B) to the hydrocarbon compound (C) [(B) / (C)] is 20 / 80 to 80 / 20.
7. 2. The resin composition according to claim 1, wherein the weight ratio of the thermoplastic resin (A) to the hydrocarbon compound (C) [(A) / (C)] is 40 / 60 to 95 / 5.
8. 2. The resin composition according to claim 1, wherein the melting point of the hydrocarbon compound (C) is 35 to 100° C.
9. 2. The resin composition according to claim 1, wherein the molecular weight of the hydrocarbon compound (C) is 500 or less.
10. The resin composition according to any one of claims 1 to 9, which is used as an agricultural biodegradable material.
Citation Information
Patent Citations
Decomposable coated granular fertilizer and its production
JP1997263476A
Thermoplastic resin composition, film and material for substrate
JP2004323797A